Understanding quinclorac resistance in Echinochloa: A comprehensive review of the biology, evolution, and management strategies - Muhammad Zia Ul Haq; Sheng Qiang (Crop Protection, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Partitioning of granular flows at valley bifurcation under varying control conditions - Hasnain Gardezi; Xingyue Li; Yu Huang; Syed Muhammad Mudassir Zia; Irtza Ali; Taimur Mazhar Sheikh (Engineering Geology, 2026)

Achieving high-quality and safe compost: a study on multi-optimization of a non-linear system using machine learning - Yuchang Shi; Muhammad Fahad Sardar; Longmei Qiu; Binxu Li; Muhammad Zia-ur-Rehman; Yukun Xue; Xu Zhang; Wuyang Zhao; Hongna Li (Bioresource Technology, 2026)

Influence of chloride, sulphate, phosphate, and silicate-based potassium fertilizers and rice husk biochar on cadmium fate, complexation, leaching and uptake in maize under alkaline soil conditions - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Mujahid Ali; Muhammad Younas; Hesham F. Alharby; Ali Majrashi; Amnah M. Alamri; Amal A. M. Al-ghamdi (Biodegradation, 2026)

Nitrogen stabilizers and crop rotation affect chemical properties and relative abundance of nitrification and denitrification genes in boreal podzolic soils - Irfan Mushtaq; Svetlana Yurgel; Zia-ul Islam; Yeukai Katanda; Muhammad Nadeem; Raymond Thomas; Lakshman Galagedara; Mumtaz Cheema (Science of The Total Environment, 2026)

Retraction notice to “Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat; a life cycle study” [Environ. Res. 216 (2023)114397] - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2026)

Synergistic charge-size trimetallic design PVDF@Mn-co/Al-LDH for efficient lithium selectivity from high-Mg/Li ratio brine - Sehria Zia; Muhammad Kashif; Haojie Ge; Yafei Guo; Tianlong Deng (Desalination, 2026)

Integrated experimental and computational insights into co-production of pectinase and xylanase from Aspergillus niger: Optimization, purification and molecular characterization - Nayya Waseem Dar; Muhammad Anjum Zia; Muhammad Shahid; Bushra Akhtar (Bioresource Technology Reports, 2026)

Energy-efficient pulsed photocatalysis with engineered biochar-ferrite nanocomposites for the reductive degradation of chlortoluron in water - Muhammad Imran; Behzad Murtaza; Muhammad Asif Naeem; Zia Ul Haq Khan; Jibran Iqbal; Muhammad Shahid; Long Li; Changseok Han (Journal of Environmental Management, 2026)

Utilizing Gamma Radiation for Sustainable Potato Farming: A Study to Enhance Potato Yield and Growth Parameters - Kalsoom Asghar Ali; Muhammad Junaid; Ashraf Ahmed Qurtam; Fahd A. Nasr; Zia-Ul-Haq (Potato Research, 2026)

Microplastic distribution and risk assessment in soil environment across Asian regions - Zia Ur Rehman; Jing Song; Chunhui Wang; Luís Miguel Nunes; Syed Shabi Ul Hassan Kazmi; Muhammad Azeem; Linxuan Fu; Yu Zhang; Gang Li (Applied Soil Ecology, 2026)

CRISPR-Cas systems for enhancing chilling tolerance in rice: recent advances and future prospects - Muhammad Sikandar Zaman; Asad Azeem; Ayesha Nouman; Abdullah Khalid; Saira Ghafoor; Muhammad Zia Ul Haq; Muhammad Talha Aslam; Hossam S. El-Beltagi (Biologia Futura, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

Effect of split applications of silicon nanoparticles and conventional sources of Si on growth, antioxidant enzymes, and cadmium uptake in wheat under Cd stress - Muhammad Aamer Maqsood; Nimra Ashraf; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Refaat A. Abohassan (South African Journal of Botany, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Enhancing Farm Productivity and Sustainability Through Maize-Soybean Intercropping with Diverse Nitrogen Management - Rukhsar Saleem; Abdul Khaliq; Muhammad Zia Ul Haq; Muhammad Aamer Maqsood (International Journal of Plant Production, 2026)

Traditional plant-based therapies in the Trans-Himalayan Cold deserts of Baltistan, Northern Pakistan - Zaheer Abbas; Shazia Kousar; Muhammad Uzair; Samuel Kelly Rees; Arshia Zia (Plant Biosystems, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Divergent physiological and biochemical strategies confer differential salinity and drought tolerance in five prevalent summer weeds - Saira Shafiq; Muhammad Zia Ul Haq; Muhammad Shahbaz; Iftikhar Ali (Biologia Futura, 2026)

Nutritional and phytochemical profiling of Solanum melongena L. root extract using LC-ESI-MS/MS; In-silico and biological evaluation - Asad Saleem Sial; Muhammad Mohtasheemul-Hasan; Khizar Abbas; Rizwana Manzoor; Usman Javaid; Syed Zia Ul Hasnain; Adnan Amin (South African Journal of Botany, 2026)

Biogenic silver-selenium nanocomposites as an effective and sustainable alternative for controlling citrus canker - Iqra Ilyas; Hammad Ul Hassan; Naveed Iqbal Raja; Zia-Ur-Rehman Mashwani; Hossam S. El-Beltagi; Muhammad Sheeraz Ahmad; Huma Qureshi; Tauseef Anwar; Muhammad Iqbal; Khalid H. Alamer; Nazih Y. Rebouh; Bakhrom Jobborov; et al. (Physiological and Molecular Plant Pathology, 2026)

Application of MnS nanoparticles in field conditions elevates morpho-physio-biochemical characteristics and oil content in Eruca sativa L. (Arugula) - Jehangir Khan; Mah Rukh; Nizakat Bibi; Joham Sarfraz Ali; Muhammad Zia (Vegetos, 2026)

Surveillance of citrus canker: a threat to Pakistani citrus industry-status and distribution of citrus canker in major citrus growing regions of Pakistan - Safi Ullah; Zia ur Rehman; Muhammad Tayyab; Aamir Iqbal; Abdullah Jalal; Jinbiao Ma; Muhammad Awais; Sajid Ali (Journal of Plant Pathology, 2026)

Legume-based diversified cropping systems increase soil organic carbon labile pools and microbial carbon use efficiency in a 12-year long-term field trial - Muhammad Nadeem Ashraf; Zawar Haider; Muhammad Ahmed Waqas; Zia Ur Rahman Farooqi; Muhammad Sanaullah; Daniel Blackburn; Zhifeng Yan; Munazza Yousra; Ansa Rebi; Allah Nawaz (Journal of Soils and Sediments, 2026)

Performance Investigation of ML Algorithms for Potato Blight Classification: The Role of Hyperparameter Tuning - Sadia Saeed; Hafiz Zia Ur Rehman; Muhammad Ureed Hussain; Muhammad Umer Khan; Muhammad Tallal Saeed (Journal of Crop Health, 2026)

Hydroxytyrosol-encapsulated solid lipid nanoparticles mitigate induced arthritis via modulating the cytokines and MMP-13 expression and downregulating oxidative stress in rats - Noor ul Huda; Aftab Ahmad; Muhammad Anjum Zia; Bushra Akhtar (Inflammopharmacology, 2026)

Assessing Genetic Variation and Population Connectivity in Wallago attu: A Call for Enhanced Conservation Measures - Taqwa Safdar; Khalid Abbas; Cedric Gondro; Sajid Abdullah; Muhammad Anjum Zia (Biochemical Genetics, 2026)

Biochar pyrolysis temperature determines the efficacy of 3, 4-dimethylpyrazole phosphate (DMPP) in reducing N2O emissions from low cadmium-contaminated paddy soil - Muhammad Laeeq Ur Rehman HASHMI; Muhammad Zia Ur Rahman HASHMI; Yasir HAMID; Bilal HUSSAIN; Tang SHENG; Wenjie LIU; Adnan ARSHAD; Tingqiang LI (Pedosphere, 2026)

Root traits and rhizosphere responses as emerging bioindicators of microplastic pollution in agricultural soils: A review - Qudsia Saeed; Xiankai Lu; Zia Ur Rahman Farooqi; Abdul Ghafoor; Muhammad Naveed; Nimra Maqsood; Hafiz Abdul Kareem; Adnan Mustafa (Environmental Research, 2026)

AI-powered automated building façade segmentation and BIPV system potential prediction using CycleGAN and PVGIS - Mohammed Sadeq; Firdaus Muhammad-Sukki; Md Zia Ullah; Nazmi Sellami (Energy and Buildings, 2026)

Chitosan-mediated elicitation enhanced production of secondary metabolites and antioxidant assays in callus culture of Ocimum bacilicum L. (Purple Basil) - Gouhar Zaman; Samah Saleh Al-Shybany; Muhammad Naeem Bajwa; Muhammad Salman Khan; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Impact of CuS Nanoparticles on Morpho-Biochemical Traits and Yield in Two Oilseed Crops; Eruca Sativa and Linum Usitatissimum - Jehangir Khan; Mah Rukh; Saad Hanif; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Fabrication, Characterization, and Effects of CuS Nanoparticles as Nano-Fertilizers on the Morphological, Biochemical Responses, and Bioaccumulation of Metal in Soybean (Glycine Max L.) and Sesame (Sesamum Indicum L.) - Jehangir Khan; Anila Sajjad; Khalid Khan; Ihsan Ullah; Syed Hamza Safeer; Muhammad Zia (Journal of Soil Science and Plant Nutrition, 2026)

Gypsum and Manure Impacts on Contrasting Textured Saline-Sodic Soils and Greenhouse Gas Emissions - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Muhammad Sabir; Aftab Jamal; Ayesha Abdul Qadir; Bryan G. Hopkins; Muhammad Nadeem Ashraf (Journal of Soil Science and Plant Nutrition, 2026)

Alleviation of Lead Stress in Maize Plants Through the Application of Green-Synthesized Zinc Oxide Nanoparticles - Haseeba Maryam; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Zia-ur-Rehman; Muhammad Atif Irshad; Saher Javed; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Is Critical Period for Weed Control Influenced by the Application of Pre-emergence Herbicide in Lentil (Lens culinaris Medik.)? - Muhammad Zia Ul Haq; Anas Ali; Gul Zaib Hassan; Rana Nadeem Abbas; Saira Shafiq; Mubashar Nadeem (International Journal of Plant Production, 2026)

Chitosan Mitigates Heat Stress in BT Cotton by Activating Antioxidant Defense System and Improving Water Relations - Abdul Shakoor; Muhammad Farrukh Saleem; Muhammad Zia Ul Haq; Muhammad Shahbaz Farooq; Muhammad Shahid (International Journal of Plant Production, 2026)

Integrative Taxonomic Study Reveals Tricholomopsis habibii sp. nov. from Swat District, Khyber Pakhtunkhwa, Pakistan - Zia Ullah; Sana Jabeen; Muhammad Faisal; Fauzia Razzaq; Hira Ijaz; Abdul Nasir Khalid (New Zealand Journal of Botany, 2026)
Tricholomopsis habibii sp. nov. has been described and illustrated, based on collections made from the Swat District, Khyber Pakhtunkhwa, Pakistan. This species differs from Tricholomopsis badinensis by its large (70–100 mm), dull brown to pale yellow pileus with a flattened umbo, lacrymoid to ellipsoid, oblong in side view basidiospores, and small (39.9–51.7 × 6.9–8. μm) cheilocystidia. The nuclear ribosomal internal transcribed spacer region and a portion of the nuclear ribosomal large subunit (28S) of this species were sequenced and analyzed which confirmed the identity of T. habibii as a new taxon.

Dissecting Microplastics Stress: Impacts of Type, Size, and Dose on Nutrient Cycling, Growth, and Antioxidant Defense System in Maize Plant - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Aamer Maqsood; Saddam Hussain (Water, Air, & Soil Pollution, 2026)

Root microstructural traits regulate ion homeostasis in bush morning glory (Ipomoea carnea Jacq.) for invasiveness success in saline environments - Syed Mohsan Raza Shah; Naila Hadayat; Jazab Shafqat; Mansoor Hameed; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Maham Zia; Zaheer Abbas; Zahida Parveen; Muhammad Ashraf; Ummar Iqbal; Ansa Asghar; et al. (The Science of Nature, 2026)

Effect of CuS NPs on growth, productivity, and biochemical characteristics and oil profile of Sesamum indicum L. under field trials - Jehangir Khan; Ihsan Ullah; Anila Sajjad; Muhammad Zia (Journal of Crop Science and Biotechnology, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Hematological Modulation and Growth Optimization in Ctenopharyngodon idella through Sorghum Diets supplemented with Chromium Chloride hexahydrate - Gulnaz Zia; Rehana Iqbal; Hamid Manzoor; Muhammad Afzaal; Sumaira Rasul; Muhammad Khalid (Biological Trace Element Research, 2026)

Assessing the impact of nano-pollutants on the growth and development of stream breeding frogs - Isma Maqbool; Laraib Khadija; Muhammad Rais; Anila Rahim; Luqman; Muhammad Naveed Iqbal Raja; Zia-ur-Rehman Mashwani; Muhammad Shahbaz; Sumbul Gill; Muhammad Saeed (Biologia, 2026)

Comparative analysis of combustion behavior of raw and torrefied biomass pellets in a customized high-temperature flat flame furnace - Khuda Bukhsh; Rui Li; Muhammad Bilal Ahmad; Yunzeng Zhao; Zhongfa Hu; Shuangling Yue; Tedla Medhane Embaye; Xiandong Li; Zia ur Rahman; Xuebin Wang; Shuanghui Deng; Zongqing Bai (Fuel, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Aspergillus Welwitschiae Regulates Response of Wheat at Multiple Levels To Alleviate Induced Chromate Stress - Urooj Jamal; Zia Ur Rahman; Muhammad Qadir; Muhammad Hamayun; Sajid Ali; Anwar Hussain (Current Microbiology, 2026)

Navigating climate policy uncertainty: how innovation and institutional quality drive GHG emissions reduction in G7 countries - Muhammad Asif; Muhammad Azam Zia; Mughair Aslam Bhatti (Clean Technologies and Environmental Policy, 2026)

Evaluation of the preventive effects of turmeric–ginger–oregano supplementation on DMBA-induced breast cancer in Sprague-Dawley rats - Nadeem Anwar; Salma Sultana; Muhammad Ashir Zia (Advances in Traditional Medicine, 2025)

Morphological, Biochemical, Yield, and Metal Accumulation Response of Eruca sativa (L.) and Linum usitatissimum (L.) by MnS NPs Application - Jehangir Khan; Mah Rukh; Saad Hanif; Amina Afzal; Muhammad Zia (Journal of Plant Growth Regulation, 2025)

From genes to fields: Genetic determinants and tillage practices shaping cereal root systems for sustainable productivity - Asad Azeem; Sami Ul-Allah; Sana Khan; Muhammad Zia Ul Haq; Muhammad Sikandar Zaman; Syed Ali Murtaza Gallani (Rhizosphere, 2025)

Corrosion control in carbon storage by injection of sodium formate solution - Doguhan Barlas Sevindik; Oluwafemi Precious Oyenowo; Ryosuke Okuno; Muhammad Farooq Zia; Bo Zhang (International Journal of Greenhouse Gas Control, 2025)

Photo-mediated synthesis of Ag/ZnO Nanocomposite: A sustainable green approach for enhanced hydrogen production and photocatalytic degradation - Asif Khalil; Muhammad Zia Ur Rehman Faurooqi; Maryam Khalid; Tanveer Farid; Saghir Hussain; Khalid Mahmood (Fuel, 2025)

Apple peel fermentation by Lactobacillus plantarum: Phytochemical transformations and enhanced abilities against inhibition of advanced glycation end products - Muhammad Nawaz; Hafiz Muhammad Rizwan; Zia Ud Din Momand; Irfan Ullah; Jiayi He; Qian Zhou; Mingfu Wang (Food Chemistry, 2025)

Nutritional, pharmaceutical, and health benefits of sunflower seeds (Helianthus annuus L.): A comprehensive review of food applications - Salah Laaraj; Ashiq Hussain; Emaan Shahid; Fozia Bakhtawar; Muhammad Zia; Ayesha Najam; Nabeela Zulfiqar; Sherouk Hussein Sweilam; Abdelaziz Ed-Dra; Kaoutar Elfazazi (Food and Humanity, 2025)

Dynamics of urinary tract infections: a comprehensive study on antimicrobial susceptibility, virulence profiling and molecular epidemiology of uropathogenic Escherichia coli from Pakistan - Zia Ashraf; Muhammad Hidayat Rasool; Bilal Aslam; Hasan Ejaz; Fatima Mujahid; Mohsin Khurshid (Molecular Biology Reports, 2025)

Evaluation of hepatic cancer stem cells (CD73+, CD44+, and CD90+) induced by diethylnitrosamine in male rats and treatment with biologically synthesized silver nanoparticles - Amber Pervez; Behramand Khan; Gul Nabi Khan; Sumayya Khattak; Mazhar Ali; Komal Mujeeb; Bushra Nasib; Hyung Goo Kim; Irfan Zia Qureshi; Muhammad Arshad (Molecular Biology Reports, 2025)

Organic Amendments Enhance Growth and Antioxidative Responses of Wheat (Triticum aestivum L.) Under Water Stress Conditions - Muhammad Tayyab Mehmood; Muhammad Anwar-ul-Haq; Muhammad Zia-ur-Rehman; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Acid-Modified Biochar Mitigates Salt Stress in Maize by Enhancing Nutrient Availability and Antioxidant Defense System Under Variable Salt-Affected Soils - Hiba Shaghaleh; Tahira Akram; Muhammad Zia-ur-Rehman; Muhammad Usman; Yousef Alhaj Hamoud; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Basmah M. Alharbi; Awatif M. Abdulmajeed (Journal of Soil Science and Plant Nutrition, 2025)

Exploring the Synergistic Benefits of Sugarcane Intercropping with Legumes and Nitrogen Reduction on System Productivity - Abdul Khaliq; Muhammad Zia Ul Haq; Abdul Khaliq; Ghulam Murtaza (International Journal of Plant Production, 2025)

Green technology, digital transformation, and energy efficiency: driving carbon reduction and waste management innovation in G20 Countries - Muhammad Asif; Muhammad Azam Zia; Muhammad Hashim; Uzair Aslam Bhatti (Clean Technologies and Environmental Policy, 2025)

Advanced PDMS@Li/ZnAl-LDH microspheres for lithium recovery from Qarhan Salt Lake brine with high Mg/Li disparity - Sehria Zia; Muhammad Kashif; Haojie Ge; Kaiyu Zhao; Yafei Guo; Tianlong Deng (Desalination, 2025)

High-performance clay and K2CO3-Modified sludge biochar for efficient reactive black-5 Removal: Mechanistic insights and alleviation of phytotoxicity - Muhammad Arif; Guijian Liu; Muhammad Zia-ur-Rehman; Qumber Abbas; Aniqa Ashraf; Muhammad Saqib Rashid; Krzysztof Pikon; Balal Yousaf (Biomass and Bioenergy, 2025)

Evaluating soil health and aggregation potential in dryland soils under diverse land uses in semiarid Pakistan - Abdul Wahab; Kashif Ali Kubar; Muhammad Shaaban; Zia-ul-hassan; Inayatullah Rajpar; Allah Wadhayo Gandahi; Saleem Maseeh Bhatti; Muhammad Afzal Chhajro; Qambar Baloch (Environmental Monitoring and Assessment, 2025)

Airborne particulate matter reduction through developed dust control systems for wheat thresher - Talha Mehmood; Zia- Ul-Haq; Tahir Iqbal; Muhammad Ansar (Air Quality, Atmosphere & Health, 2025)

The nexus between global value chains and productivity gains of ASEAN countries - Zia Ur Rahman; Wajid Khan; Musarat Abbas; Fatima Gulzar; Muhammad Azhar Farooq (Environment, Development and Sustainability, 2025)

Fe-modified biochar-driven ROS generation in the rhizosphere and their role in microplastic transformation - Zulqarnain Haider Khan; Han Yu; Hui Li; Syed Shabi Ul Hassan Kazmi; Ruixia Han; Muhammad Azeem; Xin Sun; Zia Ur Rehman; Gang Li (Journal of Hazardous Materials, 2025)

Evaluation of growth performance and metabolic efficiency in Labeo rohita fed a sorghum-based diet supplemented with chromium chloride hexahydrate - Gulnaz Zia; Rehana Iqbal; Hamid Manzoor; Muhammad Afzaal; Muhammad Khalid (Aquaculture International, 2025)

Molecular Simulation and Expression Analysis of Vitamin C and Curcumin in Mitigating Buprofezin-induced Genotoxicity and Inflammatory Responses in Balb/c Mice - Haleema Sadia; Irfan Zia Qureshi; Muhammad Naveed; Tariq Aziz; Manal F. Elkhadragy; Maher S. Alwethaynani; Fahad Al-Asmari; Areej A Alhhazmi; Hanan Abdulrahman Sagini; Suad Hamdan Almasoudi; Fakhria A. Al-Joufi (Cell Biochemistry and Biophysics, 2025)

Integration of machine learning and time series analysis for upwelling prediction dashboard in lake Laut tawar, indonesia: A study based on climate forecasting - Muhammad Zia Ulhaq; Muhammad Farid; Zahra Ifma Aziza; Teuku Muhammad Faiz Nuzullah; Fakhrus Syakir; Novi Reandy Sasmita (Theoretical and Applied Climatology, 2025)

Unleashing the Prospects of Value-Added Soil Amendments for Remediation of Salt-Affected Soils and Carbon Storage - Zia Ur Rahman Farooqi; Ayesha Abdul Qadir; Anam Naz; Waqas Mohy-Ud-Din; Elaheh Daghighi; Muhammad Tauseef Jaffar; Muhammad Ahmed; Hayssam M. Ali; Waleed A. A. Alsakkaf (Journal of Soil Science and Plant Nutrition, 2025)

Performance evaluation of mortar with high-volume cement replacement using locally sourced pumice and recycled glass waste - Muhammad Ali Wazir; Zia Ul islam; Hamzah Mohammed Ali; Osama Wali (Innovative Infrastructure Solutions, 2025)

Unlocking complex interplay between economic growth, trade openness, financial development, environmental degradation, and environmental sustainability in Bangladesh and Pakistan - Ayesha Khan; Muhammad Zia ur Rehman; Sajjad Ahmad Baig; Muhammad Usman (Environment, Development and Sustainability, 2025)

Synergistic modulation of band structure and phonon transport for higher thermoelectric performance of WSe2 - Mazhar Hussain Danish; Amil Aligayev; Zahir Muhammad; Tao Chen; Adil Mansoor; Zia Ur Rahman; F.J. Dominguez-Gutierrez; Di Li; Jian Zhang; Zhuang-Hao Zheng; Xiaoying Qin (Chemical Engineering Journal, 2025)

Foliar Application of Ascorbic Acid and α-Tocopherol Enhances Salinity Tolerance in Hordeum vulgare L. by Regulating Antioxidant Enzymatic Activity and Improving Physiological and Biochemical Responses - Sadaf; Sami Ullah; Sikandar Shah; Aftab Jamal; Adil Mihoub; Muhammad Farhan Saeed; Iftikhar Ahmad; Emanuele Radicetti; Adil Zia; Andrea Mastinu; Jakub Černý (Journal of Crop Health, 2025)
Soil salinity severely impairs crop productivity by disrupting physiological and biochemical processes. This study investigated the efficacy of foliar-applied ascorbic acid (AsA) and α‑tocopherol (α-toc) in enhancing salinity tolerance in barley ( Hordeum vulgare L. cv. AJJ). A pot experiment using a randomized complete block design with three replicates was conducted under controlled conditions. Seedlings at the 4–5 leaf stage were exposed to 0, 40, or 80 mM NaCl salinity stress, followed by foliar treatments of AsA and α‑toc (150 mg L⁻ 1 ). Germination, agronomic, physiological, and biochemical parameters were analyzed. Salinity stress at 40 and 80 mM NaCl significantly reduced germination percentage (GP) by 18.6% and 18.4%, respectively, compared to the control (86.6%). Foliar application of AsA + α-toc under 40 and 80 mM stress restored GP to 82.3% and 81.7%, reflecting recoveries of 16.8% and 15.6% overstressed groups. Water content in leaves, shoots, and roots declined by 10–30% under salinity but improved by 15–25% with AsA + α-toc. Photosynthetic pigments were severely affected: chlorophyll a and total chlorophyll content (TCC) decreased by 45.7% (1.75 to 0.95 mg g⁻ 1 FW) and 10.9% (1.75 to 1.56 mg g⁻ 1 FW) at 40 and 80 mM NaCl, respectively. AsA + α-toc mitigated these losses, elevating TCC by 42.6% under 80 mM stress. Soluble protein content increased by 186% (0.50 to 1.43 mg g⁻ 1 ) under 80 mM stress but was stabilized by antioxidant treatments. Antioxidant enzymes, including superoxide dismutase (SOD) and peroxidase (POD), surged by 40–60% under salinity, while AsA + α-toc reduced hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) levels by 30–50%. The combined application of AsA and α‑toc proved most effective, enhancing stress tolerance through improved osmotic regulation, antioxidant defense, and chlorophyll preservation. These findings highlight the potential of AsA and α‑toc as sustainable agronomic tools for cultivating barley in saline soils, with AsA showing marginally greater efficacy. Further field studies are warranted to validate these results under different climatic conditions.

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

Tegoprazan: a novel, highly selective, and potent potassium-competitive acid blocker (P-CAB) - Wenlu Wang; Hafiza Sidra Yaseen; Xiaoji Li; Muhammad Zia Ahmad; Yaowu Chen; Guorong Li; Muhammad Naveed; Hafiz Muhammad Zubair; Jannat Bibi (European Journal of Clinical Pharmacology, 2025)

Investigation of geoenvironmental contamination and risks of municipal solid waste disposal sites in urban Khyber Pakhtunkhwa, Pakistan - Muhammad Ayaz Khan; Abdullah Khan; Zia ur Rahman; Azhar Rashid; Khalid Latif (Environmental Geochemistry and Health, 2025)

Long-term trends in heavy metal contamination of marine sediments in the Arabian Gulf: A meta-analysis - S. Swetha; S. Veerasingam; S. Rajendran; Hassan Hassan; Muhammad Zia U. R. Rahman Hashmi; Hamood Alsaadi; Nelson Rangel-Buitrago; Fadhil N. Sadooni (Environmental Monitoring and Assessment, 2025)
Heavy metal (HM) contamination in marine sediments is a critical environmental concern due to its potential ecological and human health impacts. This study provides a comprehensive assessment of the spatial and temporal evolution of HM contamination in Arabian Gulf sediments over a 33-year period (1991–2024). Contamination levels were evaluated using key sediment quality indices such as the contamination factor (CF), geoaccumulation index (I g ₑₒ), pollution load index (PLI), and ecological risk index (ERI) based on available meta-data. Spatial analysis revealed that marine sediments along the Iranian and Saudi Arabian coasts exhibited higher contamination levels compared to those of other Gulf countries. This elevated contamination is likely attributed to industrial discharges, oil spills and effluent releases from desalination plants. Arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) emerged as the primary toxic contributors to sediment pollution. Overall, HM contamination status in the region is predominantly low to moderate, with localized hotspots near industrialized coastal zones. The study highlights the need for scientifically informed waste management strategies to mitigate HM contamination, particularly in nearshore environments impacted by industrial activities. Furthermore, it recommends the implementation of continuous monitoring programs to track temporal trends and identify emerging contamination sources. These findings provide critical insights for environmental managers and policymakers in developing sustainable pollution mitigation frameworks and enhancing the resilience of marine ecosystems in the Arabian Gulf.

Application of chitosan, zinc oxide nanoparticles, and Aloe vera gel edible coating for the extension in shelf life of tomatoes - Shahzad Zafar Iqbal; Muhammad Waseem; Khalid Mahmood Zia; Munawar Iqbal; Osama A. Mohammed; Nakhal Amina; Guihua Cui; Ahmed S. Doghish; Mustafa A. Abdel-Reheimand; Amin Mousavi Khaneghah (Food Packaging and Shelf Life, 2025)

Revolutionizing electrochemical sensing: Ultra-sensitive non-enzymatic detection of 4-aminophenol with a novel Cu-PANI nanocomposite - Muhammad Tayyab; Abdur Rahim; Muhammad Tariq; Zia Ul Haq Khan; Sana Sabahat; Jibran Iqbal; Dalia Fouad; Abdul Qadeer; Farid S. Ataya; Lubna Sherin (Journal of Water Process Engineering, 2025)

Evaluating Vertical Distribution of Soil Salinity Patterns Across Multiple Soil Depths in a Semi-Arid Dry Region - Qambar Baloch; Kashif Ali Kubar; Punhoon Khan Korai; Shahmir Ali Kalhoro; Muhammad Bilawal Junaid; Muneer Ahmed Baloch; Zia-ul-hassan; Jawaher Alkahtani; Muhammad Abrar (Journal of Soil Science and Plant Nutrition, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Elicitation of Withania somnifera adventitious roots: in-vitro cultures for enhanced secondary metabolites synthesis - Muhammad Adil; Zohaib Younas; Ilyas Ahmad; Khalid M. Al Rohily; Zia-ur-Rehman Mashwani (Horticulture, Environment, and Biotechnology, 2025)

Novel approaches to reduce airborne pathogen infestation through dust control systems of wheat thresher - Talha Mehmood; Zia-Ul-Haq; Tahir Iqbal; Muhammad Ansar (Aerobiologia, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

Extending freshness: The efficacy of ozonation in sterilizing fresh cut Malus domestica - Rutaba Zia; Arifa Tahir; Muhammad Arshad; Naseem Akhtar (Food and Humanity, 2025)

Molecular prevalence and genetic diversity of Toxoplasma gondii in free ranging Asil hen (Gallus gallus domesticus) - Muhammad Naeem; Anees Ur Rehman; Umme Habiba; Zia Ur Rehman; Hira Muqaddas; Amna Aqdas; Turki M. Dawoud; Mohammed Bourhia; Afshan Khan; Adil Khan; Furhan Iqbal (Tropical Animal Health and Production, 2025)

Application of multiple machine learning algorithms for intelligent prediction of the strength of fine-grained natural soils - Muhammad Shahroz Khalid; Zia ur Rehman; Badee Alshameri; Zain Maqsood; Fazal Hussain; Muhammad Irslan Khalid; Syed Jamal Arbi; Abbas Haider (Arabian Journal of Geosciences, 2025)

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Response surface optimization for biodiesel production from chicken fat via transesterification process over CaO-CeO2 catalyst - Hifza Rouf; Rehana Kousar; Zia Ul Haq; Syed Muhammad Wajahat ul Hasnain; Sajjad Haider; Salahuddin Khan; Sadaf Ul Hassan (Sustainable Chemistry and Pharmacy, 2025)

Maize cultivar mixtures: a sustainable approach for weed management under reduced herbicide dose - Amina Shahbaz; Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Amar Matloob; Rizwan Maqbool; Muhammad Tayyab Hanif; Muhammad Abu Bakar Hayat (Phytoparasitica, 2025)

Long-term grass lawn management increases soil organic carbon sequestration and microbial carbon use efficiency - Muhammad Nadeem Ashraf; Irfa Mehmood; Zia Ur Rahman Farooqi; Muhammad Itazaz Hassan; Muhammad Sanaullah; Muhammad Mubashar Zafar; Khalid M. Elhindi (Environmental Monitoring and Assessment, 2025)

UBEM-SER: Role of sufficiency, efficiency and renewable in the decarbonization of commercial building stock at city scale - Usama Perwez; Muhammad Haseeb Rasool; Imran Aziz; Usman Zia (Sustainable Cities and Society, 2025)

Soil amendment with Dryopteris nigropaleacea enhances natural control of Fusarium wilt by modulating morphological, biochemical, and physiological traits of tomato plants - Faisal Iqbal Jafri; Muhammad Akbar; Muhammad Zia ur Rehman; Mohsin Khurshid (Physiological and Molecular Plant Pathology, 2025)

Expression and characterization of the immunogenicity of rec-gp45 of Babesia bigemina using cattle - Zia-Ul-Rehman; Sarfraz-ur-Rahman; Kamran Ashraf; Muhammad Suleman; Sikandar Ali; Muhammad Imran Rashid (Tropical Animal Health and Production, 2025)

Enhancing Wheat Yield and Zinc Biofortification through Synergistic Action of Potent Zinc-Solubilizing Bacteria and Zinc Sulfate in Calcareous Soil - Murad Ali; Iftikhar Ahmed; Munir Hussain Zia; Saira Abbas; Tariq Sultan; Muhammad Sharif (Agricultural Research, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Prevalence and herd-level risk factors associated with Brucella infection in smallholders keeping large ruminants - Abrar Hussain; Sabir Hussain; Mamoona Chaudhry; Muhammad Asif Ali; Ibrahim Elsohaby; Ubaid-ur-Rehman Zia; Olivier Sparagano (Research in Veterinary Science, 2025)

Effects of polyphenols from Tasmannia lanceolata on structural, emulsifying, and antioxidant properties of pea protein - Woojeong Kim; Muhammad Bin Zia; Rishi Ravindra Naik; Kacie K.H.Y. Ho; Cordelia Selomulya (Food Chemistry, 2025)

Integrated Weed Management in Sunflower Using a Hybrid Mixture and Reduced Herbicide Dose - Gul Zaib Hassan; Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Shahid Ibni Zamir; Amina Shahbaz; Muhammad Saqib (Journal of Crop Health, 2025)

Particle size of wheat straw from genetically improved wheat affects the production performance and feeding behavior of Sahiwal cows - Muhammad Farhan Ayaz Chishti; Muhammad Aziz ur Rahman; Muhammad Qamar Bilal; Muhammad Riaz; Muhammad Farooq Khalid; Zia-Ur-Rehman; Urooj Anwar; Riaz Mustafa; Waseem Abbas; Umar Farooq (Tropical Animal Health and Production, 2025)

Mitigating lead (Pb) toxicity in Zea mays (L.) plants using green synthesized iron oxide nanoparticles - Haseeba Maryam; Muhammad Rizwan; Nasir Masood; Muhammad Waseem; Temoor Ahmed; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Humera Aziz (South African Journal of Botany, 2024)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Bioderived carbon quantum dots boost maize growth and photosynthesis by augmenting UV spectrum absorption and carbon assimilation regulatory genes - Zulqarnain Haider; Chunyan Yang; Irshan Ahmad; Samta Zia; Muhammad Haseeb Javaid; Muhammad Rehman; Muhammad Umair Yasin; Bahar Ali; Chen Nana; Yinbo Gan (Journal of Environmental Chemical Engineering, 2024)

Pre-emergence herbicide selection for successful cultivation of black seed (Nigella sativa L.), psyllium (Plantago ovata Forsk), and quinoa (Chenopodium quinoa Willd.) - Muhammad Zia Ul Haq; Saira Shafiq; Muhammad Zia Ul Mohsin; Majid Ali; Abdul Khaliq; Rana Nadeem Abbas; Muhammad Zafar Iqbal; Amar Matloob (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Biochemical, Physiological, and Nutrient Acquisition Response of Wheat Cultivars to Nickel and Vanadium Toxicity - Maria Tehseen; Houneida Attia; Abdul Khaliq; Muneera A. Saleh; Muhammad Zia Ul Haq; Khalid H. Alamer; Bader Ijaz; Iftikhar Ali; Shaista Perveen; Saddam Hussain (Journal of Plant Growth Regulation, 2024)

Removal of chlorpyrifos from aqueous medium using Ca-CuO@clay nanoflakes coated with deep eutectic solvent - Abdullah Zia; Umer Younas; Zahid Ali; Rabia Nazir; Faisal Ali; Aemin Irfan; Muhammad Pervaiz (Environmental Monitoring and Assessment, 2024)

Occurrence, spatial distribution and ecological risk assessment of Organophosphate Esters in surface water and sediments from the Ravi River and its tributaries - Samra Naseem; Amtul Bari Tabinda; Mujtaba Baqar; Mehroze Ahmad Khan; Muhammad Zia-ur-Rehman (Science of The Total Environment, 2024)

An electrochemical sensing potential of cobalt oxide nanoparticles towards citric acid integrated with computational approach in food and biological media - Huma Ajab; Ali Turab Jafry; Hasnain Sajid; Matthew A. Addicoat; Khurshid Ayub; Muhammad Zia Ul Haq (Food Chemistry, 2024)

Comparative growth, biochemical and antioxidative response of Glycine max and Sesamum indicum to MnS nanoparticles - Jehangir Khan; Anila Sajjad; Mah Rukh; Khalid Khan; Syed Waqas Hassan; Muhammad Zia (Biocatalysis and Agricultural Biotechnology, 2024)

Exposure Levels, Health Risks, Spatially Distribution, Multivariate Statistics and Positive Matrix Factorization Model of Heavy Metals from Wild solid Waste Dumpsites - Predrag Ilić; Svetlana Ilić; Abdur Rashid; Zain Mushtaq; Sanja Mrazovac Kurilić; Ljiljana Stojanović Bjelić; Dragana Nešković Markić; Zia Ur Rahman Farooqi; Muhammad Yousuf Jat Baloch; Tariq Mehmood; Zahid Ullah; Sobia Riaz (Water, Air, & Soil Pollution, 2024)

Eco-toxicological impacts of industrial wastewater and the role of bio-electrochemical systems (BES) in remediation: a review - Muhammad Usman; Zhenhua Zhao; Olive Mekontchou Yemele; Muhammad Ibrahim; Waleed Raza; Zia Ur Rehman; Abduelrahman Adam Omer; Mir Moazzam Ali Talpur; Mouna Jeridi; Ghulam Abbas Ashraf; Hafsat Alhassan Danjaji (Clean Technologies and Environmental Policy, 2024)

Understanding the spatiotemporal distribution of aerosols and their association with natural and anthropogenic factors over Saudi Arabia using multi-sensor remote sensing data - Muhammad Khan; Salman Tariq; Zia Ul Haq; Mehnaz Rashid (Air Quality, Atmosphere & Health, 2024)

Recent advances in the detection and quantification of manufactured nanoparticles (MNPs) in complex environmental and biological matrices - Qumber Abbas; Muhammad Zia-ur-Rehman; Habib Ullah; Mehar Ahmed Mujtaba Munir; Muhammad Ubaid Ali; Amjad Ali; Krzysztof Pikon; Balal Yousaf (Journal of Cleaner Production, 2024)

Engineering of interfacial electric field by g-C3N4/ZnSnO3 heterojunction for excellent photocatalytic applications - Zia Ur Rehman; Sajid Ur Rehman; Muhammad Bilal; Faheem K. Butt; Asif Hussain; Jawad Ahmad Jrar; Kewang Zheng; Yongcai Zhang; Xiaoyong Xu; Xiaozhi Wang; Jianhua Hou (Journal of Cleaner Production, 2024)

Sorghum's potential unleashed: A comprehensive exploration of bio-energy production strategies and innovations - Muaz Ameen; Athar Mahmood; Ahmad Naeem Shahzad; Muhammad Anjum Zia; Muhammad Mansoor Javaid (Bioresource Technology Reports, 2024)

Assessing and anticipating environmental challenges in Lahore, Pakistan: future implications of air pollution on sustainable development and environmental governance - Muhammad Nasar-u-Minallah; Muhammad Jabbar; Sahar Zia; Nusrat Perveen (Environmental Monitoring and Assessment, 2024)

Surface modified ZnO NPs by betaine and proline build up tomato plants against drought stress and increase fruit nutritional quality - Saad Hanif; Snovia Farooq; Misbah Zeb Kiani; Muhammad Zia (Chemosphere, 2024)

Emerging technologies for the removal of pesticides from contaminated soils and their reuse in agriculture - Teklit Gebregiorgis Ambaye; Aydin Hassani; Mentore Vaccari; Andrea Franzetti; Shiv Prasad; Francesca Formicola; Asia Rosatelli; Muhammad Zia ur Rehman; Gunda Mohanakrishna; Sharanabasava V. Ganachari; Tejraj M. Aminabhavi; Sami Rtimi (Chemosphere, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

An Investigation of the Ultraviolet Aerosol Index and Angstrom Exponent and Their Relationship with Meteorological Parameters over Nigeria Using Satellite Remote Sensing - Muhammad Khan; Salman Tariq; Zia Ul Haq (Pure and Applied Geophysics, 2024)

Synergistic effect of biochar with gypsum, lime, and farm manure on the growth and tolerance in rice plants under different salt-affected soils - Yousef Alhaj Hamoud; Talha Saleem; Muhammad Zia-ur-Rehman; Hiba Shaghaleh; Muhammad Usman; Muhammad Rizwan; Hesham F. Alharby; Amnah M. Alamri; Faisal Al-Sarraj; Nadiyah M. Alabdallah (Chemosphere, 2024)

Recent Progress of Fluorescent Carbon Dots and Graphene Quantum Dots for Biosensors: Synthesis of Solution Methods and their Medical Applications - Rafaqat Khan; Amina Qureshi; Muhammad Azhar; Zia Ul Hassan; Sagheer Gul; Saeed Ahmad (Journal of Fluorescence, 2024)

Emerging trends to replace pesticides with nanomaterials: Recent experiences and future perspectives for ecofriendly environment - Hong Wang; Muhammad Jafir; Muhammad Irfan; Tanveer Ahmad; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Yousef Alhaj Hamoud; Hiba Shaghaleh (Journal of Environmental Management, 2024)

Spatial variation in iodine content with relation to soil physicochemical properties in lower Himalayan region - Jawad Ali; Muhammad Mohiuddin; Xinfeng Wang; Zahid Hussain; Muhammad Irshad; Munir Zia; Rashid Pervez; Mohammad K. Okla; Shakeel Ahmad (Environmental Research, 2024)

Construction and Utilization of Innovative Zeolite/Perovskite/Graphene Oxide, Zeolite/Chitosan/Graphene Oxide, and Zeolite/Biochar/Graphene Oxide Nanohybrid Composites for Adsorptive Remediation of Cationic Dye from Wastewater - Nageen Mushtaq; Ruba Munir; Muhammad Zia-ur-Rehman; Zia ul-Haq; Muhammad Zeeshan Bashir; Amna Muneer; Hina Ambreen; Saima Noreen (Water Conservation Science and Engineering, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

Correction: Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Combined Effect of Biochar and Plant Growth-Promoting Rhizbacteria on Physiological Responses of Canola (Brassica napus L.) Subjected to Drought Stress - Gul-Lalay; Sami Ullah; Sikandar Shah; Aftab Jamal; Muhammad Farhan Saeed; Adil Mihoub; Adil Zia; Iftikhar Ahmed; Mahmoud F. Seleiman; Roberto Mancinelli; Emanuele Radicetti (Journal of Plant Growth Regulation, 2024)
Biochar (BC) and plant growth-promoting microbes (PGPR) could represent a suitable agronomical strategy to mitigate the impacts of drought in arid agro-environmental conditions. However, there is currently little understanding of the synergistic benefit of combining BC and PGPR to increase drought tolerance in oilseeds. In this study, the physiological response of two water-stressed canola ( Brassica napus L.) plants subjected to the application of BC obtained from waste wood of Morus alba applied solely or in combination with PGPR strains ( Pseudomonas sp.) was evaluated. The experiment consists of two genotypes and nine treatments [(C-Control, T1-15 days drought (15DD), T2-30 days drought (30DD), T3-15 days of drought + PG (15DD + PG), T4-30 days of drought + PG (30DD + PG), T5-15 days drought + biochar (15DD + BC), T6-30 days drought + biochar (30DD + BC), T7-15 days drought + biochar + PG (15DD + BC + PG), T8-30 days drought + biochar + PG (30DD + BC + PG)]. Drought stress decreased emergence energy (EE), leaf area index (LAI), leaf area ratio (LAR), root shoot ratio (RSR), moisture content of leaves (MCL), percent moisture content (%MC), moisture content of shoot (MCS) and moisture content of root (MCR), and relative water content (RWC) in both varieties of Brassica napus L., which in contrast, it is increased by the collective application of both biochar and PGPR. In both varieties, N, P, K, Mg, and Ca concentrations were highest in all the biochar and PGPRs separate and combined treatments, while lowest in 15 and 30 days drought treatments. Osmolyte contents like Glycine betaine (GB) and sugar remarkably increased in the stress condition and then reduced due to the synergistic application of biochar and PGPR. Drought stress has a repressive effect on the antioxidant enzymatic system like Peroxidase (POD), Superoxide dismutase (SOD), and glutathione reductase (GR) as well as total flavonoids, phenolics, and protein content. The antioxidant enzymes and phenolic compounds were dramatically increased by the combined action of biochar and PGPRs. A significant increase in EE, LAR, RSR, and RWC under 15 and 30 days drought conditions, evidently highlighting the synergistic effect of BC and PGPR. The results conclude a substantial and positive effect of the combined use of BC and PGPR strains on canola's response to induced drought stress, by regulating the physiological, biochemical, and agronomic traits of the plants. Graphical Abstract

Efficacy of Different Pre and Post Emergence Herbicide Application on Late Sown Maize Crop Under Variable Planting Density - Muhammad Talha Aslam; Rizwan Maqbool; Imran Khan; Muhammad Umer Chattha; Muhammad Nawaz; Adnan Noor Shah; Muhammad Zia Ul Haq; Muhammad Nauman Gulzar; Fatmah M. Alqahtani; Mohamed Hashem; Muhammad Umair Hassan; Sezai Ercisli (International Journal of Plant Production, 2024)

First principle study of X2GaAgCl6 (X = Cs, Rb) double perovskites: structural, mechanical, vibrational, electronic, optical, SLME, thermoelectric, and thermodynamic properties for solar cell applications - Zia Ur Rehman; Muhammad Awais Rehman; Muhammad Rashid Khan; Bushra Rehman; Surajudeen Sikiru; Muhammad Rizwan; Mohammed Chafi; Muhammad Usman (Environmental Science and Pollution Research, 2024)

Empirical testing of the environmental Kuznets curve: evidence from 182 countries of the world - Muhammad Azam; Zia Ur Rehman; Himayatullah Khan; Ilham Haouas (Environment, Development and Sustainability, 2024)

Exposure to zinc oxide nanoparticles induced reproductive toxicities in male Sprague Dawley rats - Nagina Rehman; Farhat Jabeen; Muhammad Asad; Aneela Nijabat; Amir Ali; Safir Ullah Khan; Juan Pedro Luna-Arias; Zia-ur-Rehman Mashwani; Ayesha Siddiqa; Adhimoolam Karthikeyan; Ajaz Ahmad (Journal of Trace Elements in Medicine and Biology, 2024)

Cadmium Stress Alleviation: Interplay of Micronutrients and Enzymatic/Non-enzymatic Species in Maize by Organic and Inorganic Amendments - Sehar Razzaq; Beibei Zhou; Muhammad Adil; Zakir Ullah; Hongchao Guo; Muhammad Zia-Ur-Rehman; Chen Xiaopeng; Li Wen Qian; Heli Lu (Water, Air, & Soil Pollution, 2024)

An appealing review of industrial and nutraceutical applications of pistachio waste - Syed Ali Hassan; Mueen Abbas; Sania Zia; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Abdo Hassoun; Aamir Shehzad; Richard Gattin; Rana Muhammad Aadil (Critical Reviews in Food Science and Nutrition, 2024)

From field to table: Ensuring food safety by reducing pesticide residues in food - Salman Munir; Asad Azeem; Muhammad Sikandar Zaman; Muhammad Zia Ul Haq (Science of The Total Environment, 2024)

Optimized design and analysis of cable-based parallel manipulators for enhanced subsea operations - Asim Ghaffar; Muhammad Zia Ur Rahman; Víctor Leiva; Cecilia Castro (Ocean Engineering, 2024)

Utilizing a Low-Cost Air Quality Sensor: Assessing Air Pollutant Concentrations and Risks Using Low-Cost Sensors in Selangor, Malaysia - Zaki Khaslan; Mohd Shahrul Mohd Nadzir; Hamimatunnisa Johar; Zhang Siqi; Nor Azura Sulong; Faizal Mohamed; Shubhankar Majumdar; Fatin Nur Afiqah Suris; Nor Syamimi Sufiera Limi Hawari; Jintu Borah; Maggie Ooi Chel Gee; Muhammad Ikram A. Wahab; et al. (Water, Air, & Soil Pollution, 2024)

Leading report of molecular prevalence of tick borne Anaplasma marginale and Theileria ovis in yaks (Bos grunniens) from Pakistan - Muqaddas Nawaz; Rehmat Ullah; Zia Ur Rehman; Muhammad Naeem; Afshan Khan; Mohammed Bourhia; Muhammad Mudassir Sohail; Takbir Ali; Adil Khan; Tanveer Hussain; Furhan Iqbal (Archives of Microbiology, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Teat morphology across five buffalo breeds: a multi-country collaborative study - Carlo Boselli; Angela Costa; Massimo De Marchi; Muhammad A. Zia; Muhammad Q. Shahid; Nasim Ahmad; Ivan Fasulkov; Manol Karadaev; Yordanka Ilieva; Pencho Penchev; Fatemeh Derisavi; Mohammad Nikookar; et al. (Tropical Animal Health and Production, 2024)

Impact of meteorological parameters on aerosol optical depth and particulate matter in Lahore - Zahid Ur Rehman; Salman Tariq; Zia ul Haq; Muhammad Khan (Acta Geophysica, 2024)

Quantification of the effect of biochar application on heavy metals in paddy systems: Impact, mechanisms and future prospects - Yonglin Chen; Wentao Yang; Yuzheng Zou; Yuhong Wu; Wenjian Mao; Jian Zhang; Muhammad Zia-ur-Rehman; Bing Wang; Pan Wu (Science of The Total Environment, 2024)

Alleviated lead toxicity in rice plant by co-augmented action of genome doubling and TiO2 nanoparticles on gene expression, cytological and physiological changes - Fozia Ghouri; Munazzam Jawad Shahid; Minghui Zhong; Muhammad Azam Zia; Sarah Owdah Alomrani; Jingwen Liu; Lixia Sun; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Science of The Total Environment, 2024)

New trends in functionalities and extraction of plant proteins in designing plant-based meat analogues: A critical review - Aaysha Ihsan; Zia Ahmad; Jie Zheng; Muhammad Bilal; Hafiz Muhammad Rizwan Abid; Aijun Hu (Food Bioscience, 2024)

Trends and social aspects in the management and conversion of agricultural residues into valuable resources: A comprehensive approach to counter environmental degradation, food security, and climate change - Abbas Sheer; Muhammad Fahad Sardar; Fazila Younas; Pengcheng Zhu; Saima Noreen; Tariq Mehmood; Zia Ur Rahman Farooqi; Sidra Fatima; Weihua Guo (Bioresource Technology, 2024)

Role of biogas slurry to reclaim soil properties providing an eco-friendly approach for crop productivity - Asif Mukhtiar; Athar Mahmood; Muhammad Anjum Zia; Muaz Ameen; Renji Dong; Yang Shoujun; Muhammad Mansoor Javaid; Bilal Ahmad Khan; Muhammad Ather Nadeem (Bioresource Technology Reports, 2024)

Retraction Note: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia‑ur‑Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Corrigendum to “Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil” [Chemosphere 341, November (2023) 140019] - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; Amany H.A. Abeed (Chemosphere, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Global insights into micro-macro mechanisms and environmental implications of limestone calcined clay cement (LC3) for sustainable construction applications - Nauman Ijaz; Wei-Min Ye; Zia ur Rehman; Zain Ijaz; Muhammad Faisal Junaid (Science of The Total Environment, 2024)

Development and testing of environment friendly nanohybrid coatings for sustainable agriculture technologies - Bilal Beig; Muhammad Bilal Khan Niazi; Farooq Sher; Zaib Jahan; Munir Zia; Ghulam Abbas Shah; Ayman A. Ghfar; Zahid Iqbal (Environmental Research, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Exogenous application of jasmonates and brassinosteroids alleviates lead toxicity in bamboo by altering biochemical and physiological attributes - Abolghassem Emamverdian; Ahlam Khalofah; Necla Pehlivan; Muhammad Zia-ur-Rehman; Yang Li; Meisam Zargar (Environmental Science and Pollution Research, 2023)

Impact of transportation infrastructure and urbanization on environmental pollution: evidence from novel wavelet quantile correlation approach - Muhammad Usman Malik; Zia ur Rehman; Arshian Sharif; Ahsan Anwar (Environmental Science and Pollution Research, 2023)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Unlocking therapeutic potential of trigonelline through molecular docking as a promising approach for treating diverse neurological disorders - Syeda Rehana Zia; Muhammad Wasim; Saara Ahmad (Metabolic Brain Disease, 2023)

Physiological and Metabolic Changes in Maize Seedlings in Response to Bisphenol A Stress - Haziq Hussain; Rehan Naeem; Baharullah Khattak; Zia ur Rehman; Niamat Khan; Muhammad Kamran Qureshi; Farah Deeba; Iftikhar Ali; Muhammad Daud Khan (Journal of Soil Science and Plant Nutrition, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Effect of exogenous application of biogenic silicon sources on growth, yield, and ionic homeostasis of maize (Zea mays L.) crops cultivated in alkaline soil - Arwa Abdulkreem AL-Huqail; Ali Rizwan; Muhammad Zia-ur-Rehman; Haifa Abdulaziz Sakit Al-Haithloul; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Naveeda Majid; Yousef Alhaj Hamoud; Muhammad Rizwan; AmanyH.A. Abeed (Chemosphere, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Effects of zinc-enriched amino acids on rice plants (Oryza sativa L.) for adaptation in saline-sodic soil conditions: Growth, nutrient uptake and biofortification of zinc - Saqib Raza; Muhammad Zia-ur-Rehman; Sameera A. Alghamdi; Suliman Mohammed Suliman Alghanem; Muhammad Usman; Rubaz Ahmed; Aisha Abdul Waris; Muhammad Rizwan; Amany H.A. Abeed; Haifa Abdulaziz Sakit Al-Haithloul (South African Journal of Botany, 2023)

Exploring the mechanism of Cd uptake and translocation in rice: Future perspectives of rice safety - Haonan Jing; Wentao Yang; Yonglin Chen; Liyu Yang; Hang Zhou; Yang Yang; Zhenjie Zhao; Pan Wu; Muhammad Zia-ur-Rehman (Science of The Total Environment, 2023)

Proline coated ZnO NPs as nanofertilizer against drought stress: an in vitro study to Coriandrum sativum - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Synergistic effect of glycine betain-ZnO nanocomposite in vitro for the amelioration of drought stress in coriander - Saad Hanif; Anila Sajjad; Muhammad Zia (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Environmental implications of phosphate-based fertilizer industrial waste and its management practices - Noman Ahmad; Muhammad Usman; Hamaad Raza Ahmad; Muhammad Sabir; Zia Ur Rahman Farooqi; Muhammad Tahir Shehzad (Environmental Monitoring and Assessment, 2023)

Climate-induced shifts in irrigation water demand and supply during sensitive crop growth phases in South Asia - Qurat-ul-Ain Ahmad; Eddy Moors; Hester Biemans; Nuzba Shaheen; Ilyas Masih; Muhammad Zia ur Rahman Hashmi (Climatic Change, 2023)
This study investigated the shifts in irrigation water demand and supply of the major staple and water-intensive crops (wheat and rice) in the Indus, Ganges and Brahmaputra (IGB) river basins of South Asia under the combined impacts of climate change and socio-economic development during the period 1981–2100. It explores irrigation water usage during climate-sensitive crop growth phases (i.e. vegetative and reproductive which required ~ 60% of the total seasonal (sowing to harvest) water demand), which is supposed to be crucial for long-term integrated crop water management. A hydrology vegetation model Lund Potsdam Jena Managed Land is forced with an ensemble of eight downscaled (5 arc-min) global climate model’s using the RCP (Representative concentration pathways) -SSP (Shared socio-economic pathways) framework, i.e. RCP4.5-SSP1 and RCP8.5-SSP3. To investigate phase-specific crop water projections, trend analysis is performed. It shows a significant ( p <0.001) increase in irrigation water demand during the vegetative phase of wheat (6 mm) and reproductive phase of rice (26 mm) and a decrease during the reproductive phase of wheat (13 mm) and vegetative phase of rice (11 mm) in selected study sites. The large decrease in projected irrigation demand for wheat can be explained by a shortening of the growing season length as a result of rising temperatures and increased precipitation. Whereas, an increase in irrigation demand for rice is a combined effect of higher temperatures and less precipitation during the reproductive phase in the region. At the same time, irrigation supply by surface water and groundwater is likely to change in future due to warmer and drier growing periods, causing a significant increase in groundwater irrigation, mainly for rice. Our major research findings show the importance of crop water assessments during the sensitive crop growth phases of wheat and rice which vary in space and time. Including crop phase-specific, climate impact assessments of regional and global projection will help improve the region’s existing crop-water management strategies and adaptation practices.

Geospatial modeling of heterogeneous geotechnical data using conventional and enhanced conception of modified Shepard method-based IDW algorithms: application and appraisal - Zain Ijaz; Cheng Zhao; Nauman Ijaz; Zia ur Rehman; Aashan Ijaz; Muhammad Faisal Junaid (Bulletin of Engineering Geology and the Environment, 2023)

Ab initio insight into the physical properties of MgXH3 (X = Co, Cu, Ni) lead-free perovskite for hydrogen storage application - Zia ur Rehman; Muhammad Awais Rehman; Bushra Rehman; Surajudeen Sikiru; Saima Qureshi; Esraa Mousa Ali; Muhammad Awais; Mahnoor Amjad; Iqra Iqbal; Anam Rafique; Saira Bibi (Environmental Science and Pollution Research, 2023)

Corrigendum to cerium oxide nanoparticles alleviates stress in wheat grown on Cd contaminated alkaline soil [Chemosphere 338 (2023) 139561] - Muhammad Ashar Ayub; Hamaad Raza Ahmad; Muhammad Zia ur Rehman; Ejaz Ahmad Waraich (Chemosphere, 2023)

Cerium oxide nanoparticles alleviates stress in wheat grown on Cd contaminated alkaline soil - Muhammad Ashar Ayub; Hamaad Raza Ahmad; Muhammad Zia ur Rehman; Ejaz Ahmad Waraich (Chemosphere, 2023)

Biogas Energy Resources in Pakistan Status, Potential, and Barriers - Muhammad Wakeel; Tasawer Hayat; Noor Samad Shah; Jibran Iqbal; Zia Ul Haq Khan; Ghulam Mustafa Shah; Atta Rasool (Utilities Policy, 2023)

Paper based colorimetric sensor using novel green magnetized nanocomposite of pinus for hydrogen peroxide detection in water and milk - Mehrosh Buzdar; Asim Yaqub; Akhtar Hayat; Muhammad Zia Ul Haq; Aizaz Khan; Huma Ajab (Food Bioscience, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Ecological monitoring of urban thermal field variance index and determining the surface urban heat island effects in Lahore, Pakistan - Muhammad Nasar-u-Minallah; Dagmar Haase; Salman Qureshi; Sahar Zia; Munazza Fatima (Environmental Monitoring and Assessment, 2023)

How environmental protection activities and industrial revolution contributes in the nexus of energy security and environmental sustainability? - Ruoyu Zhong; Wenzong Wu; Muhammad Waqas Akbar; Zeenat Zia (Environmental Science and Pollution Research, 2023)

Recent developments and challenges in uranium extraction from seawater through amidoxime-functionalized adsorbents - Bilal Ahmed; Zia Ahmad; Amina Khatoon; Iqra Khan; Nusrat Shaheen; Attiya Abdul Malik; Zahid Hussain; Muhammad Ali Khan (Environmental Science and Pollution Research, 2023)

Correction to: Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

Effect of iron nanoparticles and conventional sources of Fe on growth, physiology and nutrient accumulation in wheat plants grown on normal and salt-affected soils - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Sidra Anayatullah; Muhammad Rizwan; Hesham F. Alharby; Isam M. Abu Zeid; Nadiyah M. Alabdallah; Shafaqat Ali (Journal of Hazardous Materials, 2023)

Copper oxide nanoparticles: In vitro and in vivo toxicity, mechanisms of action and factors influencing their toxicology - Humna Sajjad; Anila Sajjad; Rida Tul Haya; Muhammad Mustajab Khan; Muhammad Zia (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Comparative immunocompetence and interspecies transmission of avian orthoavulavirus-1 in feral birds originating from rural and urban settings - Momena Habib; Aziz Ul-Rahman; Zia-ur-Rehman; Muhammad Akbar Shahid; Noreen Sarwar; Muhammad Bilal; Muhammad Saeed Imran; Muhammad Munir; Shaista Abbas; Muhammad Zubair Shabbir (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Oxide vacancy passivation through interface engineering of Tetraphenylethylene-Based Small-Molecule with sulfonate functional group for efficient organic photodetector - Woongsik Jang; Zia Ur Rehman; Muhammad Haris; Jae Sang Cho; Jihyun Lim; Min Soo Kim; Jong-Cheol Lee; Hang Ken Lee; Dong Hwan Wang (Chemical Engineering Journal, 2023)

Transforming Bombax ceiba L. sawdust waste into a valuable growth substrate: An example with sugarcane - Muhammad Yasin; Muhammad Usman Zia; Athar Mahmood; Muhammad Mansoor Javaid; Muhammad Ather Nadeem; Christian Andreasen (Bioresource Technology Reports, 2023)

An Application of Rock Phosphate Increased Soil Cadmium Contamination and Hampered the Morphophysiological Growth of Brassica campestris L - Muhammad Usman Khadim; Ghulam Murtaza; Zia Ur Rahman Farooqi; Tajammal Hussain; Naeem Mahmood; Saddam Hussain (Journal of Soil Science and Plant Nutrition, 2023)

Nanotoxicity assessment in plants: an updated overview - Hira Zafar; Rabia Javed; Muhammad Zia (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Effect of titanium dioxide nanoparticles and co-composted biochar on growth and Cd uptake by wheat plants: A field study - Fu Chen; Yuhang Li; Muhammad Atif Irshad; Afzal Hussain; Rab Nawaz; Muhammad Farooq Qayyum; Jing Ma; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Research, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

3D and 4D Bioprinting Technologies: A Game Changer for the Biomedical Sector? - Reza Noroozi; Zia Ullah Arif; Hadi Taghvaei; Muhammad Yasir Khalid; Hossein Sahbafar; Amin Hadi; Ali Sadeghianmaryan; Xiongbiao Chen (Annals of Biomedical Engineering, 2023)

Long-term spatio-temporal trends in atmospheric aerosols and trace gases over Pakistan using remote sensing - Muhammad Adil Javed; Usman Mehmood; Salman Tariq; Zia ul Haq (Acta Geophysica, 2023)

An approach to assess offshore wind power potential using bathymetry and near-hub-height reanalysis data - Zia ul Rehman Tahir; Muhammad Abdullah; Sajeer Ahmad; Ammara Kanwal; Muhammad Farhan; Usama Bin Saeed; Tariq Ali; Imran Amin (Ocean Engineering, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

Application of portable Vis-NIR spectroscopy for rapid detection of myoglobin in frozen pork - Yanna Rong; Muhammad Zareef; Lihua Liu; Zia Ud Din; Quansheng Chen; Qin Ouyang (Meat Science, 2023)

Exogenous application of low and high molecular weight organic acids differentially affected the uptake of cadmium in wheat-rice cropping system in alkaline calcareous soil - Muhammad Zia-ur-Rehman; Manar Fawzi Bani Mfarrej; Muhammad Usman; Muhammad Azhar; Muhammad Rizwan; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Zahoor Ahmad (Environmental Pollution, 2023)

Segmentation of digital rock images using texture analysis and deep network - Shahzad Manzoor; Tehreem Qasim; Naeem Bhatti; Muhammad Zia (Arabian Journal of Geosciences, 2023)

Moderating role of attitude in strengthening the practices and behavior of ecological civilization in Pakistan - Zeenat Zia; Shuming Liu; Muhammad Waqas Akbar; Fei Meng; Yuelan Peng (Environment, Development and Sustainability, 2023)

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

Differential response of nano zinc sulphate with other conventional sources of Zn in mitigating salinity stress in rice grown on saline-sodic soil - Rubaz Ahmed; Muhammad Zia-ur-Rehman; Muhammad Sabir; Muhammad Usman; Muhammad Rizwan; Zahoor Ahmad; Hesham F. Alharby; Hassan S. Al-Zahrani; Hameed Alsamadany; Amal Y. Aldhebiani; Yahya M. Alzahrani; Atif A. Bamagoos (Chemosphere, 2023)

Preparation of amylopectin and chitosan based polyurethanes for sustained drug release studies - Muhammad Asif Javaid; Sobia Jabeen; Noureen Arshad; Khalid Mahmood Zia; Muhammad Tahir Hussain; Inam Ullah; Saliha Ahmad; Muhammad Shoaib (Sustainable Chemistry and Pharmacy, 2023)

Adsorption of hexavalent chromium ions in industrial effluent on low cost magnetized wood saw dust decayed by Isoptera (Termite): An insight into kinetics, equilibrium and thermodynamics studies - Mehpara Khatoon; Huma Ajab; Asim Yaqub; Muhammad Zia Ul Haq; Muhammad Junaid (Journal of Environmental Chemical Engineering, 2023)

Effects of silicon nanoparticles and conventional Si amendments on growth and nutrient accumulation by maize (Zea mays L.) grown in saline-sodic soil - Ali Rizwan; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Muhammad Usman; Sidra Anayatullah; Areej; Hesham F. Alharby; Atif A. Bamagoos; Basmah M. Alharbi; Shafaqat Ali (Environmental Research, 2023)

Composted Melia azedarach L. (Chinaberry tree) Sawdust Mixtures Regulate the Sprouting and Growth of Single Bud Node Seedlings of Sugarcane - Mehwish Sultan Ahmed; Muhammad Yasin; Muhammad Usman Zia; Muhammad Ather Nadeem; Sher Muhammad; Athar Mahmood (Journal of Soil Science and Plant Nutrition, 2023)

Do demographic factors affect the environment? Empirical evidence from the Middle East and North African countries - Ilham Haouas; Muhammad Haseeb; Muhammad Azam; Zia Ur Rehman (Environmental Science and Pollution Research, 2023)

Integrating wheat straw and silica fume as a balanced mechanical ameliorator for expansive soil: a novel agri-industrial waste solution - Usama Khalid; Zia ur Rehman; Nauman Ijaz; Inamullah Khan; Muhammad Faisal Junaid (Environmental Science and Pollution Research, 2023)

Zinc oxide nanoparticles coated urea enhances nitrogen efficiency and zinc bioavailability in wheat in alkaline calcareous soils - Shaiza Amin; Tariq Aziz; Muhammad Zia-ur-Rehman; Ifra Saleem; Muhammad Rizwan; Ambreen Ashar; Hafiz Adnan Mussawar; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2023)

Dose optimization of silicon for boosting arbuscular mycorrhizal fungi colonization and cadmium stress mitigation in maize (Zea mays L.) - Ubaid Ullah Zia; Abdul Rehman Niazi; Zahoor Ahmad; Hesham F. Alharby; Ejaz Ahmad Waraich; Asim Abbasi; Muhammad Aamir Iqbal; Sarfraz Ahmed; Shozab Hina (Environmental Science and Pollution Research, 2023)

Hydrothermal assisted synthesis of hierarchical SnO2 micro flowers with CdO nanoparticles based membrane for energy storage applications - Ehsan Ullah; Muhammad Zia Ullah Shah; Syed Awais Ahmad; Muhammad Sajjad; Shaukat Khan; Fatimah M. Alzahrani; Adel E.M. Yahya; Sayed M. Eldin; Bhargav Akkinepally; A. Shah; Shenghui Guo (Chemosphere, 2023)

Remediation methods of heavy metal contaminated soils from environmental and geotechnical standpoints - Zia ur Rehman; Muhammad Faisal Junaid; Nauman Ijaz; Usama Khalid; Zain Ijaz (Science of The Total Environment, 2023)

Influence of ionic cerium and cerium oxide nanoparticles on Zea mays seedlings grown with and without cadmium - Muhammad Ashar Ayub; Muhammad Zia ur Rehman; Hamaad Raza Ahmad; John-Paul Fox; Preston Clubb; Alan L. Wright; Muhammad Anwar-ul-Haq; Muhammad Nadeem; Cyren M. Rico; Lorenzo Rossi (Environmental Pollution, 2023)

Combined effects of zinc oxide nanoparticles and melatonin on wheat growth, chlorophyll contents, cadmium (Cd) and zinc uptake under Cd stress - Fu Chen; Yuhang Li; Muhammad Zia-ur-Rehman; Syed Makhdoom Hussain; Muhammad Farooq Qayyum; Muhammad Rizwan; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Shafaqat Ali (Science of The Total Environment, 2023)

Re-investigating the impact of non-renewable and renewable energy on environmental quality: A roadmap towards sustainable development - Syed Abdul Rehman Khan; Hafiz Muhammad Zia-Ul-Haq; Pablo Ponce; Laeeq Janjua (Resources Policy, 2023)

Role of empowering leadership in inducing employee green creative behavior in hotel and restaurant industry: a moderated-moderated mediation model - Muhammad Arif Khattak; Zia Ur Rehman; Shujahat Haider Hashmi (Environment, Development and Sustainability, 2023)

Variations in the aerosol index and its relationship with meteorological parameters over Pakistan using remote sensing - Muhammad Khan; Salman Tariq; Zia Ul Haq (Environmental Science and Pollution Research, 2023)

Nanoparticles assisted regulation of oxidative stress and antioxidant enzyme system in plants under salt stress: A review - Muhammad Zia-ur-Rehman; Sidra Anayatullah; Effa Irfan; Syed Makhdoom Hussain; Muhammad Rizwan; Muhammad Irfan Sohail; Muhammad Jafir; Tanveer Ahmad; Muhammad Usman; Hesham F. Alharby (Chemosphere, 2023)

Effect of farmyard manure, elemental sulphur and EDTA on growth and phytoextraction of cadmium by spider plants (Chlorophytum comosum L.) under Cd stress - Muhammad Zia-ur-Rehman; Arisha Mubsher; Muhammad Rizwan; Muhammad Usman; Muhammad Jafir; Muhammad Umair; Hesham F. Alharby; Atif A. Bamagoos; Rahma Alshamrani; Shafaqat Ali (Chemosphere, 2023)

Activated carbon derived from Dodonaea Viscosa into beads of calcium-alginate for the sorption of methylene blue (MB): Kinetics, equilibrium and thermodynamics - Asim Yaqub; Samia Misbah Syed; Huma Ajab; Muhammad Zia Ul Haq (Journal of Environmental Management, 2023)

Physiological and transcriptome analyses demonstrate the silver nanoparticles mediated alleviation of salt stress in pearl millet (Pennisetum glaucum L) - Imran Khan; Samrah Afzal Awan; Muhammad Rizwan; Muhammad Adnan Akram; Muhammad Zia-ur-Rehman; Xiaosan Wang; Xinquan Zhang; Linkai Huang (Environmental Pollution, 2023)

Alleviation of drought stress and mediated antioxidative defense in wheat through moringa leaf extract hormesis - Muhammad Usman Ibrahim; Abdul Khaliq; Saddam Hussain; Muhammad Zia Ul Haq (Arabian Journal of Geosciences, 2023)

Effects of Mirabilis jalapa L. root extract and sildenafil on paroxetine-induced sexual dysfunction in male rats and characterization of its phytoconstituents by UPLC-MS - Asad Ur Rahman; Fiaz Alam; Zia Ur Rehman; Muhammad Khan; Tawseef Ahmad (South African Journal of Botany, 2023)

Different feedstocks of biochar affected the bioavailability and uptake of heavy metals by wheat (Triticum aestivum L.) plants grown in metal contaminated soil - Muhammad Ahmar Amin; Ghulam Haider; Muhammad Rizwan; H. Kate Schofield; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Shafaqat Ali (Environmental Research, 2023)

RETRACTED: Effect of soil texture and zinc oxide nanoparticles on growth and accumulation of cadmium by wheat: a life cycle study - Muhammad Usman; Muhammad Zia-ur-Rehman; Muhammad Rizwan; Tahir Abbas; Muhammad Ashar Ayub; Asif Naeem; Hesham F. Alharby; Nadiyah M. Alabdallah; Basmah M. Alharbi; Muhammad Javid Qamar; Shafaqat Ali (Environmental Research, 2023)

An overview of genome-wide association mapping studies in Poaceae species (model crops: wheat and rice) - Muhammad Abu Bakar Zia; Muhammad Farhan Yousaf; Arslan Asim; Muhammad Naeem (Molecular Biology Reports, 2022)

Diospyros malabarica (Desr.) Kostel fruits extract attenuated acute and chronic inflammation through modulation of the expression of pro- and anti-inflammatory biomarkers in rat models - Saba Zia; Mohammad Saleem; Muhammad Asif; Khalid Hussain; Beenish Zia Butt (Inflammopharmacology, 2022)

Biomagnification of potentially toxic elements in animals consuming fodder irrigated with sewage water - Ghulam Murtaza; Muhammad Tahir Shehzad; Sobia Kanwal; Zia Ur Rahman Farooqi; Gary Owens (Environmental Geochemistry and Health, 2022)

Causal nexus in industrialization, urbanization, trade openness, and carbon emissions: empirical evidence from OPEC economies - Muhammad Azam; Zia Ur Rehman; Yusnidah Ibrahim (Environment, Development and Sustainability, 2022)

Environmental sustainability and green technologies across BRICS countries: the role of institutional quality - Zeenat Zia; Liu Shuming; Muhammad Waqas Akbar; Tauqeer Ahmed (Environmental Science and Pollution Research, 2022)

Chemical composition, antibacterial and antioxidative activities of Monotheca buxifolia (Falc.) A. DC leaves essential oil - Joham Sarfraz Ali; Muhammad Azeem; Abdul Mannan; Muhammad Zia (Natural Product Research, 2022)

Types, sources, socioeconomic impacts, and control strategies of environmental noise: a review - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Allah Ditta; Predrag Ilic; Muhammad Amin; Abdul Basit Naveed; Aadil Gulzar (Environmental Science and Pollution Research, 2022)

Foliar spray of silicon nanoparticles improved the growth and minimized cadmium (Cd) in wheat under combined Cd and water-limited stress - Muhammad Adrees; Zahra Saeed Khan; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2022)

Strengthening potential of xanthan gum biopolymer in stabilizing weak subgrade soil - Muhammad Hamza; Zhihong Nie; Mubashir Aziz; Nauman Ijaz; Zain Ijaz; Zia ur Rehman (Clean Technologies and Environmental Policy, 2022)

RETRACTED ARTICLE: Ameliorative effect of two structurally divergent hydrazide derivatives against DSS-induced colitis by targeting Nrf2 and NF-κB signaling in mice - Ashrafullah Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Sajjad Ahmad; Muhammad Usman Amin; Muhammad Naeem Ahmed; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Analyzing the determinants of sustainability of China Pakistan Economic Corridor (CPEC) projects: an interpretive structural modelling (ISM) approach - Maryam Farooq; Zia-ur-Rehman Rao; Muhammad Shoaib (Environmental Science and Pollution Research, 2022)

Dye Wastewater Treatment Using Wheat Straw Biochar in Gadoon Industrial Areas of Swabi, Pakistan - Muhammad Tariq; Shams Ali Baig; Dilawar Farhan Shams; Sayed Hussain; Rahib Hussain; Abdul Qadir; Hafiza Seerat Maryam; Zia Ullah Khan; Shehla Sattar; Xinhua Xu (Water Conservation Science and Engineering, 2022)

Antioxidant, antimicrobial, enzyme inhibition, and cytotoxicity guided investigation of Sideroxylon mascatense (A.DC.) T.D. Penn. leaves extracts - Joham Sarfraz Ali; Naheed Riaz; Abdul Mannan; Muhammad Latif; Muhammad Zia (Natural Product Research, 2022)

Toxicity of selected organophosphate and pyrethroid insecticides against larval and adult stages of Culex quinquefasciatus - Muhammad Zubair; Hafiz Azhar Ali Khan; Waseem Akram; Khurram Zia; Rana Muhammad Naeem Ahsan; Malik Muhammad Shahbaz Sharif; Huma Qamar; Muhammad Kamil Malik (International Journal of Tropical Insect Science, 2022)

Apportionment of heavy metals in a soil–water-plant system via brick kiln emissions in heavily industrialized city of Pakistan - Imran Ahmad; Hamaad Raza Ahmad; Zia Ur Rahman Farooqi; Muhammad Sabir; Muhammad Rizwan; Muhammad Aamer Maqsood (Environmental Science and Pollution Research, 2022)

Does energy use and economic growth allow for environmental sustainability? An empirical analysis of Pakistan - Muhammad Mohsin; Sobia Naseem; Muddassar Sarfraz; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2022)

Striving towards sustainable development: how environmental degradation and energy efficiency interact with health expenditures in SAARC countries - Ruoyu Zhong; Xuedi Ren; Muhammad Waqas Akbar; Zeenat Zia; Robert Sroufe (Environmental Science and Pollution Research, 2022)

Effect of soil amendments and varied soil texture on wheat growth, physiology, and nutrient accumulation at different salinity: sodicity levels - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Arabian Journal of Geosciences, 2022)

Application of Gypsum or Sulfuric Acid Improves Physiological Traits and Nutritional Status of Rice in Calcareous Saline-Sodic Soils - Ayesha Abdul Qadir; Ghulam Murtaza; Muhammad Zia-ur-Rehman; Ejaz Ahmad Waraich (Journal of Soil Science and Plant Nutrition, 2022)

Nexus between disaggregated energy sources, institutional quality, and environmental degradation in BRI countries: a penal quantile regression analysis - Muhammad Waqas Akbar; Ruoyu Zhong; Zeenat Zia; Junaid Jahangir (Environmental Science and Pollution Research, 2022)

Arsenic concentrations in soil, water, and rice grains of rice-growing areas of Punjab, Pakistan: multivariate statistical analysis - Muhammad Tahir Shehzad; Muhammad Sabir; Muhammad Zia-ur-Rehman; Muhammad Anjum Zia; Ravi Naidu (Environmental Monitoring and Assessment, 2022)

Meteorological trend analysis for Najd and Hejaz regions, Saudi Arabia - Ateeq-ur-Rauf; Navid Ahmad; Muhammad Ajmal; Abdul Malik; Zia ur Rahman (Meteorology and Atmospheric Physics, 2022)

Triggering sustainable firm performance, supply chain competitive advantage, and green innovation through lean, green, and agile supply chain practices - Muhammad Waqas; Xue Honggang; Naveed Ahmad; Syed Abdul Rehman Khan; Zia Ullah; Muzaffar Iqbal (Environmental Science and Pollution Research, 2022)

The influence of energy consumption and economic growth on environmental degradation in BRICS countries: an application of the ARDL model and decoupling index - Sobia Naseem; Muhammad Mohsin; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muddassar Sarfraz (Environmental Science and Pollution Research, 2022)

Establishing a corporate social responsibility implementation model for promoting sustainability in the food sector: a hybrid approach of expert mining and ISM–MICMAC - Muhammad Shahjahan Usmani; Jianling Wang; Naveed Ahmad; Zia Ullah; Muzaffar Iqbal; Muhammad Ismail (Environmental Science and Pollution Research, 2022)

Structural and Functional Annotation of Napin-Like Protein from Momordica charantia to Explore its Medicinal Importance - Rawaba Arif; Muhammad Anjum Zia; Ghulam Mustafa (Biochemical Genetics, 2022)

Green bond as a new determinant of sustainable green financing, energy efficiency investment, and economic growth: a global perspective - Yiyi Ning; Jacob Cherian; Muhammad Safdar Sial; Susana Álvarez-Otero; Ubaldo Comite; Malik Zia-Ud-Din (Environmental Science and Pollution Research, 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

Anti-neuropathic pain activity of a cationic palladium (II) dithiocarbamate by suppressing the inflammatory mediators in paclitaxel-induced neuropathic pain model - Muhammad Naveed; Rahim Ullah; Adnan Khan; Bushra Shal; Ashraf Ullah Khan; Shahan Zeb Khan; Zia ur Rehman; Salman Khan (Molecular Biology Reports, 2021)

Effects of selenium on the uptake of toxic trace elements by crop plants: A review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Jörg Rinklebe; Daniel C. W. Tsang; Filip M. G. Tack; Ghulam Hasan Abbasi; Afzal Hussain; Avanthi Deshani Igalavithana; Byung Cheon Lee; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2021)

Heavy Metals Accumulation in Dragonflies (Odonata) and Their Habitats in District Swabi, Khyber Pakhtunkhwa, Pakistan: Assessing Dragonfly Bionomics in the Region - Hajra Noor-Ul-Islam; Khurshaid Khan; Syed Ahmed Zia; Muhammad Naeem; Waqas Ahmad Shams (Bulletin of Environmental Contamination and Toxicology, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Urban noise assessment and its nonauditory health effects on the residents of Chiniot and Jhang, Punjab, Pakistan - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Nukshab Zeeshan; Predrag Ilić; Muhammad Imran; Muhammad Farhan Saeed (Environmental Science and Pollution Research, 2021)

Striving towards environmental sustainability: how natural resources, human capital, financial development, and economic growth interact with ecological footprint in China - Sayma Zia; Mustaghis ur Rahman; Mohammed Hassan Noor; Muhammad Kamran Khan; Munaza Bibi; Danish Iqbal Godil; Muhammad Umer Quddoos; Muhammad Khalid Anser (Environmental Science and Pollution Research, 2021)

Knowledge, attitude, and practices associated with brucellosis among livestock owners and its public health impact in Punjab, Pakistan - Sabir Hussain; Abrar Hussain; Ubaid-ur-Rehman Zia; Syed Musa Raza Naqvi; Muhammad Yasir Zahoor; Muhammad Bilal; Jeffery HO; Olivier A. E. Sparagano (Biologia, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Phytochemical and spectral analysis of the methanolic extracts of leaves of Murraya koenigii of Jazan, Saudi Arabia - Sivakumar Sivagurunthan Moni; Muhammad Hadi Sultan; Hafiz A. Makeen; Aamena Jabeen; Syeda Sanobar; Rahimullah Siddiqui; Zia ur Rehman; Md Shamsher Alam; Sarfaraz Ahmad; Mohamed Eltaib Elmobark; Remesh Moochikkal (Natural Product Research, 2021)

The nexus of sectoral-based CO2 emissions and fiscal policy instruments in the light of Belt and Road Initiative - Muhammad Waqas Akbar; Peng Yuelan; Adnan Maqbool; Zeenat Zia; Muhammad Saeed (Environmental Science and Pollution Research, 2021)

Effect of green human resource management practices on organizational sustainability: the mediating role of environmental and employee performance - Fiza Amjad; Waseem Abbas; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muhammad Hashim; Ayesha Khan; Hakeem-ur- Rehman (Environmental Science and Pollution Research, 2021)

Distribution and health risk assessment of trace elements in ground/surface water of Kot Addu, Punjab, Pakistan: a multivariate analysis - Zafar Abbas; Muhammad Imran; Natasha Natasha; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Iftikhar Ahmad; Sajjad Ahmad (Environmental Monitoring and Assessment, 2021)

Synergistic influence of CuO nanoparticles and spectral lights transforms biomass, antioxidative response, and antioxidants in Brassica nigra - Muhammad Zia; Hira Zafar; Faiza Zarrin Gul; Bilal Haider Abbasi; Zarrin Fatima Rizvi; Abdul Mannan (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Solvent extraction, spectral analysis and antibacterial activity of the bioactive crystals of Sargassum aquifolium (Turner) C.Agardh from Red Sea - Sivakumar Sivagurunathan Moni; Mohammad Firoz Alam; Hafiz A. Makeen; Hassan A. Alhazmi; Muhammad Sultan; Rahimullah Siddiqui; Aamena Jabeen; Syeda Sanobar; Md Shamsher Alam; Zia Ur Rehman; Mohamed Eltyep Elmobark; Osama Madkhali; et al. (Natural Product Research, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Surface water quality assessment of Skardu springs using Water Quality Index - Wazir Aitizaz Ahsan; Hamaad Raza Ahmad; Zia Ur Rahman Farooqi; Muhammad Sabir; Muhammad Ashar Ayub; Muhammad Rizwan; Predrag Ilic (Environmental Science and Pollution Research, 2021)

Remote Sensing of Narrowing Barrier Islands along the Coast of Pakistan over Past 30 Years - Shamsa Kanwal; Xiaoli Ding; Muhammad Sajjad; Majid Nazeer; Ibrahim Zia (Journal of Marine Science and Engineering, 2021)
Barrier islands (BIs) are the first line of defense against the sea/wave actions in coastal areas, and assessing their stability is crucial in the context of effective coastal planning. Therefore, this study evaluates the spatial–temporal shoreline changes of the BIs in Pakistan over the past three decades (1989–2018). Satellite data from Landsat missions are used to delineate the shorelines of 19 BIs in Pakistan. After delineating the shorelines from satellite observations, two well-known statistical methods (i.e., end point rate (EPR) and linear regression rate (LRR)) are used to capture the localized changes in the BIs. The results ascertain that nearly all of the BIs have experienced noteworthy erosion during the past three decades. While the mean erosion over all the BIs during the study period is estimated to be >6 m/y, significant spatial heterogeneities among the individual BIs exist. The interdecadal comparison indicates that the highest mean erosion of the BIs occurred during the period 1989–1999 (13.03 ± 0.62 m/y), which gradually reduced over the preceding decades (i.e., 7.76 ± 0.62 m/y during the period 1999–2009 and 3.8 ± 0.7 m/y during the period 2009–2018). Nevertheless, ~65% of the total BIs experienced high erosion (>2 m/y), ~15% experienced moderate (

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Impact of heat stress responsive factors on growth and physiology of cotton (Gossypium hirsutum L.) - Muhammad Asif Saleem; Waqas Malik; Abdul Qayyum; Sami Ul-Allah; Muhammad Qadir Ahmad; Hammad Afzal; Muhammad Waqas Amjid; Muhammad Farjad Ateeq; Zia Ullah Zia (Molecular Biology Reports, 2021)

Does the modifying role of institutional quality remains homogeneous in GDP-CO2 emission nexus? New evidence from ARDL approach - Usman Mehmood; Salman Tariq; Zia Ul-Haq; Muhammad Saeed Meo (Environmental Science and Pollution Research, 2021)

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

Effect of biochar and compost on cadmium bioavailability and its uptake by wheat–rice cropping system irrigated with untreated sewage water: a field study - Muhammad Zia ur Rehman; Maqsooda Waqar; Safdar Bashir; Muhammad Rizwan; Shafaqat Ali; Ahmed Abd El Fattah El Baroudy; Hinnan Khalid; Muhammad Ashar Ayub; Muhammad Usman; Shah Jahan (Arabian Journal of Geosciences, 2021)

Quantification and risk assessment of heavy metal build-up in soil–plant system after irrigation with untreated city wastewater in Vehari, Pakistan - Tania Sarwar; Muhammad Shahid; Natasha; Sana Khalid; Ali Haidar Shah; Naveed Ahmad; Muhammad Asif Naeem; Zia ul Haq; Behzad Murtaza; Hafiz Faiq Bakhat (Environmental Geochemistry and Health, 2020)

Unraveling the effects of cadmium on growth, physiology and associated health risks of leafy vegetables - Junaid Latif; Javaid Akhtar; Iftikhar Ahmad; Muhammad Mahmood-ur-Rehman; Ghulam Mustafa Shah; Qamaruz Zaman; Tariq Javaid; Zia Ur Rahman Farooqi; Muhammad Shakar; Azka Saleem; Muhammad Rizwan (Brazilian Journal of Botany, 2020)

Retraction Note to: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2020)

Risk assessment of hazardous elements in wastewater irrigated soil and cultivated vegetables in Pakistan - Alia Naz; Sardar Khan; Said Muhammad; Rafiq Ahmad; Salma Khalid; Abdullah Khan; Rashid Nazir; Sadia Alam; Zia ur Rahman (Arabian Journal of Geosciences, 2020)

Effect of gibberellic acid on growth, biomass, and antioxidant defense system of wheat (Triticum aestivum L.) under cerium oxide nanoparticle stress - Azka Iftikhar; Muhammad Rizwan; Muhammad Adrees; Shafaqat Ali; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Afzal Hussain (Environmental Science and Pollution Research, 2020)

Biological and phytochemical studies on Capparis decidua (Forssk) Edgew from Cholistan desert - Shazia Anjum; Muhammad Asif; Kashaf Zia; Bakhat Jahan; Muhammad Ashraf; Shafqat Hussain; Muhammad Qasim Hayat; Muhammad Raza Shah; Muhammad Nawaz Tahir (Natural Product Research, 2020)

Synthesis and characterization of poly(N-isopropylmethacrylamide-acrylic acid) smart polymer microgels for adsorptive extraction of copper(II) and cobalt(II) from aqueous medium: kinetic and thermodynamic aspects - Khalida Naseem; Zahoor H. Farooqi; Robina Begum; Muhammad Zia Ur Rehman; Maida Ghufran; Weitai Wu; Jawayria Najeeb; Ahmad Irfan (Environmental Science and Pollution Research, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Effect of composted organic amendments and zinc oxide nanoparticles on growth and cadmium accumulation by wheat; a life cycle study - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2020)

Genome-wide association study identifies various loci underlying agronomic and morphological traits in diversified potato panel - Muhammad Abu Bakar Zia; Ufuk Demirel; Muhammad Azhar Nadeem; Mehmet Emin Çaliskan (Physiology and Molecular Biology of Plants, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Identification of stripe rust resistant genes and their validation in seedling and adult plant glass house tests - Shamaila Tahir; Iram Zia; Iqra Dilshad; Muhammad Fayyaz; Nighat Noureen; Sumaira Farrakh (Genetic Resources and Crop Evolution, 2020)

Anticancer and antibacterial potential of Rhus punjabensis and CuO nanoparticles - Sania Naz; Saira Tabassum; Nelson Freitas Fernandes; Mohammad Mujahid; Muhammad Zia; Esperanza J. Carcache de Blanco (Natural Product Research, 2020)

Regeneration response of carnation cultivars in response of silver nanoparticles under in vitro conditions - Muhammad Zia; Kamran Yaqoob; Abdul Mannan; Sobia Nisa; Ghulam Raza; Riaz ur Rehman (Vegetos, 2020)

Antimicrobial, cytotoxic, phytochemical and biological properties of crude extract and solid phase fractions of Monotheca buxifolia - Joham Sarfraz Ali; Ihsan Khan; Muhammad Zia (Advances in Traditional Medicine, 2020)

Effects of silicon nanoparticles on growth and physiology of wheat in cadmium contaminated soil under different soil moisture levels - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Adrees; Muhammad Farooq Qayyum; Sofia Khalid; Muhammad Zia ur Rehman; Muhammad Aleem Sarwar (Environmental Science and Pollution Research, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Assessment of noise pollution and its effects on human health in industrial hub of Pakistan - Zia Ur Rahman Farooqi; Muhammad Sabir; Junaid Latif; Zubair Aslam; Hamaad Raza Ahmad; Iftikhar Ahmad; Muhammad Imran; Predrag Ilić (Environmental Science and Pollution Research, 2020)

Thidiazuron-induced efficient biosynthesis of phenolic compounds in callus culture of Ipomoea turbinata Lagasca and Segura - Waqar Ahmad; Adnan Zahir; Muhammad Nadeem; Muhammad Zia; Christophe Hano; Bilal Haider Abbasi (In Vitro Cellular & Developmental Biology - Plant, 2019)

Influence of biochar amendment and foliar application of iron oxide nanoparticles on growth, photosynthesis, and cadmium accumulation in rice biomass - Muhammad Rizwan; Shamaila Noureen; Shafaqat Ali; Sarwat Anwar; Muhammad Zia ur Rehman; Muhammad Farooq Qayyum; Azhar Hussain (Journal of Soils and Sediments, 2019)

The nexus of fiscal policy instruments and environmental degradation in China - Peng Yuelan; Muhammad Waqas Akbar; Muhammad Hafeez; Manzoor Ahmad; Zeenat Zia; Sana Ullah (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Hepatitis E outbreak in the province of Punjab, Pakistan: a call for action - Muhammad Salman; Zia Ul Mustafa; Noman Asif (Infectious Diseases, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Cadmium immobilization in the soil and accumulation by spinach (Spinacia oleracea) depend on biochar types under controlled and field conditions - Muhammad Farooq Qayyum; Rabia Abdur Rehman; Seemab Liaqat; Muhammad Ikram; Shafaqat Ali; Muhammad Rizwan; Muhammad Zia ur Rehman; Muhammad Zafar-ul-Hye; Qaiser Hussain (Arabian Journal of Geosciences, 2019)

Ultrasonic assisted improved extraction and dyeing of mordanted silk fabric using neem bark as source of natural colourant - Shahid Adeel; Khalid Mahmood Zia; Muhammad Abdullah; Fazal-ur- Rehman; Mahwish Salman; Mohammad Zuber (Natural Product Research, 2019)

Development of Whey Protein Concentrate-Pectin-Alginate Based Delivery System to Improve Survival of B. longum BL-05 in Simulated Gastrointestinal Conditions - Iqra Yasmin; Muhammad Saeed; Imran Pasha; Muhammad Anjum Zia (Probiotics and Antimicrobial Proteins, 2019)

Opportunities and challenges in the remediation of metal-contaminated soils by using tobacco (Nicotiana tabacum L.): a critical review - Muhammad Zia ur Rehman; Muhammad Rizwan; Muhammad Irfan Sohail; Shafaqat Ali; Aisha A. Waris; Hinnan Khalid; Asif Naeem; Hamaad Raza Ahmad; Arslan Rauf (Environmental Science and Pollution Research, 2019)

Correction to: Effect of foliar applications of silicon and titanium dioxide nanoparticles on growth, oxidative stress, and cadmium accumulation by rice (Oryza sativa) - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Sumaira Malik; Muhammad Adrees; Muhammad Farooq Qayyum; Saud A. Alamri; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Acta Physiologiae Plantarum, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

A critical review on the effects of zinc at toxic levels of cadmium in plants - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Arosha Maqbool (Environmental Science and Pollution Research, 2019)

Effect of foliar applications of silicon and titanium dioxide nanoparticles on growth, oxidative stress, and cadmium accumulation by rice (Oryza sativa) - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Sumaira Malik; Muhammad Adrees; Muhammad Farooq Qayyum; Saud A. Alamri; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Acta Physiologiae Plantarum, 2019)

Modeling Sugar Beet Response to Different Combinations of On-Farm Water Management Practices Under Semi-arid Sub-tropical Environment - Abdul Malik; Abdul Sattar Shakir; Muhammad Jamal Khan; Muhammad Ajmal; Muhammad Shahzad Khattak; Taj Ali Khan; Zia Ul Haq; Mahmood Alam Khan; Naeem Ijaz (Sugar Tech, 2019)

Chemical investigations of Si-rich organic and inorganic amendments and correlation analysis between different chemical composition and Si contents in amendments - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Ghulam Murtaza; Muhammad Ashfaq Wahid (Arabian Journal of Geosciences, 2019)

Correction to: Preparation, optimization and pharmacological evaluation of 99mTc-4-hydroxy-3-(2-hydroxy-3-methoxybenzylideneamino) benzoic acid complex: as a novel potential radiopharmaceutical agent with hepatobiliary excretion - Muhammad Usman Akbar; Tanveer Hussain Bokhari; Samina Roohi; Khalid Mahmood Zia; Muhammad Razeen Ahmad; Saira Hina; Muhammad Sohaib (Molecular Biology Reports, 2018)

Deadly outbreak of chickenpox at district Faisalabad, Pakistan: possible causes, and preventive way forward - Muhammad Zubair Yousaf; Sadia Zia; Khalid Mahmood Anjum; Usman Ali Ashfaq; Muhammad Imran; Samia Afzal; Muhammad Sarfaraz Iqbal (Molecular Biology Reports, 2018)

Role of Zinc–Lysine on Growth and Chromium Uptake in Rice Plants under Cr Stress - Afzal Hussain; Shafaqat Ali; Muhammad Rizwan; Muhammad Zia ur Rehman; Amjad Hameed; Farhan Hafeez; Saud A. Alamri; Mohammed Nasser Alyemeni; Leonard Wijaya (Journal of Plant Growth Regulation, 2018)

Performance of silver, zinc, and iron nanoparticles-doped cotton filters against airborne E. coli to minimize bioaerosol exposure - Attarad Ali; Maohua Pan; Trevor B. Tilly; Muhammad Zia; Chang Yu Wu (Air Quality, Atmosphere & Health, 2018)

Cadmium (Cd) concentration in wheat (Triticum aestivum) grown in Cd-spiked soil varies with the doses and biochar feedstock - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Irfan Sohail; Amjad Hussain; Muhammad Farooq Qayyum; Hinnan Khalid; Muhammad Zeeshan; Naveeda Majid (Arabian Journal of Geosciences, 2018)

Residual impact of biochar on cadmium uptake by rice (Oryza sativa L.) grown in Cd-contaminated soil - Muhammad Rizwan; Shafaqat Ali; Tahir Abbas; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Effect of biochar on alleviation of cadmium toxicity in wheat (Triticum aestivum L.) grown on Cd-contaminated saline soil - Tahir Abbas; Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Yong Sik Ok; Ghulam Murtaza (Environmental Science and Pollution Research, 2018)

Effects of biochar on growth, photosynthesis, and chromium (Cr) uptake in Brassica rapa L. under Cr stress - Shafaqat Ali; Muhammad Rizwan; Ruqia Bano; Saima Aslam Bharwana; Muhammad Zia ur Rehman; Muhammad Bilal Hussain; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Correction to: Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

Anti-inflammatory, anti-rheumatic and analgesic activities of 2-(5-mercapto-1,3,4-oxadiazol-2-yl)-N-propylbenzenesulphonamide (MOPBS) in rodents - Hina Rasheed; Ruqayya Afridi; Ashraf Ullah Khan; Muhammad Zia Ullah; Sidra Khalid; Ayesha Atiq; Humaira Kashif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammopharmacology, 2018)

A critical review of mechanisms involved in the adsorption of organic and inorganic contaminants through biochar - Zohaib Abbas; Shafaqat Ali; Muhammad Rizwan; Ihsan Elahi Zaheer; Afifa Malik; Muhammad Ahsan Riaz; Muhammad Rizwan Shahid; Muhammad Zia ur Rehman; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Pluronic-Based Mixed Polymeric Micelles Enhance the Therapeutic Potential of Curcumin - Muhammad Usman Akbar; Khalid Mahmood Zia; Ahsan Nazir; Jamshed Iqbal; Syeda Abida Ejaz; Muhammad Sajid Hamid Akash (AAPS PharmSciTech, 2018)

Effect of foliar-applied iron complexed with lysine on growth and cadmium (Cd) uptake in rice under Cd stress - Arooj Bashir; Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Wajid Ishaque; Muhammad Atif Riaz; Arosha Maqbool (Environmental Science and Pollution Research, 2018)

Molecular investigation of foot-and-mouth disease virus circulating in Pakistan during 2014-17 - Waqas Ali; Mudasser Habib; Rai Shafqat Ali Khan; Muhammad Ashir Zia; Muhammad Farooq; Sanaullah Sajid; Muhammad Salah Ud Din Shah (Archives of Virology, 2018)

Lead Toxicity in Cereals and Its Management Strategies: a Critical Review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Muhammad Rizwan Javed; Arooj Bashir (Water, Air, & Soil Pollution, 2018)

Identification, Characterization and Expression Profiles of Dof Transcription Factors in Pineapple (Ananas comosus L) - Syed Muhammad Azam; Yanhui Liu; Zia Ur Rahman; Hina Ali; Cheng Yan; Lulu Wang; S. V. G. N. Priyadarshani; Binyan Hu; Xinyu Huang; Junjie Xiong; Yuan Qin (Tropical Plant Biology, 2018)

New natural product -an efficient antimicrobial applications of new newly synthesized pyrimidine derivatives by the electrochemical oxidation of hydroxyl phenol in the presence of 2-mercapto-6-(trifluoromethyl) pyrimidine-4-ol as nucleophile - Zia Ul Haq Khan; Amjad Khan; Pingyu Wan; Arif Ullah Khan; Kamran Tahir; Nawshad Muhammad; Faheem Ullah Khan; Hidayat Ullah Shah; Zia Ullah Khan (Natural Product Research, 2018)

Elicitation of Secondary Metabolites in Callus Cultures of Stevia rebaudiana Bertoni Grown Under ZnO and CuO Nanoparticles Stress - Rabia Javed; Buhara Yucesan; Muhammad Zia; Ekrem Gurel (Sugar Tech, 2018)

Microwave-assisted extraction and dyeing of chemical and bio-mordanted cotton fabric using harmal seeds as a source of natural dye - Shahid Adeel; Muhammad Zuber; Fazal-ur-Rehman; Khalid Mahmood Zia (Environmental Science and Pollution Research, 2018)

Management of tannery wastewater for improving growth attributes and reducing chromium uptake in spinach through citric acid application - Arosha Maqbool; Shafaqat Ali; Muhammad Rizwan; Wajid Ishaque; Nasir Rasool; Muhammad Zia ur Rehman; Arooj Bashir; Muhammad Abid; Longhua Wu (Environmental Science and Pollution Research, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

Comparison of total ozone column observations from space-borne Ozone Monitoring Instrument with ground-based Dobson Ozone Spectrophotometer measurements at an urban location in Indo-Gangetic Basin - Zia Ul-Haq; Zertasha Ramzan; Salman Tariq; Syeda Adila Batool; Muhammad Ali; Javed Sami (International Journal of Remote Sensing, 2018)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

Assessment of sea water inundation along Daboo creek area in Indus Delta Region, Pakistan - Ibrahim Zia; Hina Zafar; Muhammad I. Shahzad; Mohsin Meraj; Jamil H. Kazmi (Journal of Ocean University of China, 2017)

Effects of co-composting of farm manure and biochar on plant growth and carbon mineralization in an alkaline soil - Muhammad Farooq Qayyum; Fatima Liaquat; Rabia Abdur Rehman; Mehreen Gul; Muhammad Zafar ul Hye; Muhammad Rizwan; Muhammad Zia ur Rehaman (Environmental Science and Pollution Research, 2017)

Contrasting Effects of Organic and Inorganic Amendments on Reducing Lead Toxicity in Wheat - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Sabir; Muhammad I. Sohail (Bulletin of Environmental Contamination and Toxicology, 2017)

Spatiotemporal patterns of correlation between atmospheric nitrogen dioxide and aerosols over South Asia - Zia ul-Haq; Salman Tariq; Muhammad Ali (Meteorology and Atmospheric Physics, 2017)

Differential effects of plant growth regulators on physiology, steviol glycosides content, and antioxidant capacity in micropropagated tissues of Stevia rebaudiana - Rabia Javed; Buhara Yucesan; Muhammad Zia; Ekrem Gurel (Biologia, 2017)

Erratum to: An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Molecular characterization of previously elusive badnaviruses associated with symptomatic cacao in the New World - Nomatter Chingandu; Muhammad Zia-ur-rehman; Thyail N. Sreenivasan; Surendra Surujdeo-Maharaj; Pathmanathan Umaharan; Osman A. Gutierrez; Judith K. Brown (Archives of Virology, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Use of Maize (Zea mays L.) for phytomanagement of Cd-contaminated soils: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Zia-ur-Rehman; Zaheer Abbas; Fakhir Hannan (Environmental Geochemistry and Health, 2017)

Satellite-sensed tropospheric NO 2 patterns and anomalies over Indus, Ganges, Brahmaputra, and Meghna river basins - Zia ul-Haq; Salman Tariq; Muhammad Ali; Asim Daud Rana; Khalid Mahmood (International Journal of Remote Sensing, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Determination of Serum Trace Elements (Zn, Cu, and Fe) in Pakistani Patients with Rheumatoid Arthritis - Zia Ullah; Muhammad Ikram Ullah; Shabbir Hussain; Haiba Kaul; Khalid P. Lone (Biological Trace Element Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Ameliorative effect of synthetic γ-aminobutyric acid (GABA) on performance traits, antioxidant status and immune response in broiler exposed to cyclic heat stress - Naila Chand; Sher Muhammad; Rifat Ullah Khan; Ibrahim Abdullah Alhidary; Zia ur Rehman (Environmental Science and Pollution Research, 2016)

An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2016)

Bioavailability evaluation, uptake of heavy metals and potential health risks via dietary exposure in urban-industrial areas - Balal Yousaf; Guijian Liu; Ruwei Wang; Muhammad Imtiaz; Muhammad Zia-ur-Rehman; Mehr Ahmed Mujtaba Munir; Zhiyuan Niu (Environmental Science and Pollution Research, 2016)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

Cadmium stress in rice: toxic effects, tolerance mechanisms, and management: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Hina Rizvi; Muhammad Zia-ur-Rehman; Fakhir Hannan; Muhammad Farooq Qayyum; Farhan Hafeez; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Emission quantification of refrigerant CFCs, HCFCs and HFCs in megacity Lahore (Pakistan) and contributed ODPs and GWPs - Zia Ul-Haq; Muhammad Ali; Syeda Adila Batool; Salman Tariq; Zarmina Qayyum (Journal of Earth System Science, 2016)

Sulphur dioxide loadings over megacity Lahore (Pakistan) and adjoining region of Indo-Gangetic Basin - Zia ul-Haq; Salman Tariq; Muhammad Ali; Khalid Mahmood; Asim Daud Rana (International Journal of Remote Sensing, 2016)

Molecular characterization of infectious bursal disease viruses from Pakistan - Muhammad Zubair Shabbir; Muhammad Ali; Muhammad Abbas; Umer Naveed Chaudhry; Zia-ur-Rehman; Muhammad Munir (Archives of Virology, 2016)

Effects of industrial wastewater on growth and biomass production in commonly grown vegetables - Syeda Uzma; Azizullah Azizullah; Roqaia Bibi; Farhat Nabeela; Uzair Muhammad; Imran Ali; Zia Ur Rehman; Donat-Peter Häder (Environmental Monitoring and Assessment, 2016)

Alleviation of lead-induced physiological, metabolic, and ultramorphological changes in leaves of upland cotton through glutathione - Mumtaz Khan; M. K. Daud; Ali Basharat; Muhammad Jamil Khan; Azizullah Azizullah; Niaz Muhammad; Noor Muhammad; Zia ur Rehman; Shui Jin Zhu (Environmental Science and Pollution Research, 2016)

Mechanisms of biochar-mediated alleviation of toxicity of trace elements in plants: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Muhammad Ibrahim; Muhammad Zia-ur-Rehman; Tahir Abbas; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

Satellite and ground-based remote sensing of aerosols during intense haze event of October 2013 over lahore, Pakistan - Salman Tariq; ul-Haq Zia; Muhammad Ali (Asia-Pacific Journal of Atmospheric Sciences, 2016)

New furocarbazole alkaloids from Lonicera quinquelocularis - Dilfaraz Khan; Shafiullah Khan; Syed Badshah; Hazrat Ali; Hamid Ullah; Zia Muhammad; Simon Woodward (Natural Product Research, 2016)

Effect of inorganic amendments for in situ stabilization of cadmium in contaminated soils and its phyto-availability to wheat and rice under rotation - Muhammad Zia-ur Rehman; Muhammad Rizwan; Abdul Ghafoor; Asif Naeem; Shafaqat Ali; Muhammad Sabir; Muhammad Farooq Qayyum (Environmental Science and Pollution Research, 2015)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Assessment of heavy metals and metalloids in tissues of two frog species: Rana tigrina and Euphlyctis cyanophlyctis from industrial city Sialkot, Pakistan - Irfan Zia Qureshi; Zeshan Kashif; Muhammad Zaffar Hashmi; Xiaomei Su; Riffat Naseem Malik; Kalim Ullah; Jinxing Hu; Muhammad Dawood (Environmental Science and Pollution Research, 2015)

Potato Starch as a Coagulant for Dye Removal from Textile Wastewater - Muhammad Shahzad Zafar; Muhammad Tausif; Muhammad Mohsin; Syed Waqas Ahmad; Muhammad Zia-ul-Haq (Water, Air, & Soil Pollution, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Impact of Drought Stress on Some Grain Quality Traits in Rice (Oryza sativa) - Zulqarnain Haider; Umar Farooq; Imad Naseem; Samta Zia; Muhammad Alamgeer (Agricultural Research, 2015)

Response of nitrogen assimilating enzymes during in vitro culture of Argyrolobium roseum - Darima Habib; Muhammad Zia; Yamin Bibi; Bilal Haider Abbasi; Muhammad Fayyaz Chaudhary (Biologia, 2015)

Satellite remote sensing of total ozone column (TOC) over Pakistan and neighbouring regions - Zia Ul-Haq; Salman Tariq; Asim Daud Rana; Muhammad Ali; Khalid Mahmood; Parvez Shahid (International Journal of Remote Sensing, 2015)

Effect of oxytocin on serum biochemistry, liver enzymes, and metabolic hormones in lactating Nili Ravi buffaloes - Zafar Iqbal; Zia ur Rahman; Faqir Muhammad; Masood Akhtar; Mian Muhammad Awais; Tanweer Khaliq; Amar Nasir; Muhammad Nadeem; Kinza Khan; Hafiz Muhammad Arshad; Muhammad Abdul Basit (Tropical Animal Health and Production, 2015)

Upgrade of egg quality through different heat-combating systems during high environmental temperature - Muhammad Safdar Anjum; Mansur Abdullah Sandhu; Nasir Mukhtar; Zia-ur Rahman (Tropical Animal Health and Production, 2014)

In vitro propagation of Caralluma tuberculata and evaluation of antioxidant potential - Riaz Ur Rehman; Muhammad Fayyaz Chaudhary; Khalid Mahmood Khawar; Gang Lu; Abdul Mannan; Muhammad Zia (Biologia, 2014)

A study of aerosol properties over Lahore (Pakistan) by using AERONET data - Muhammad Ali; Salman Tariq; Khalid Mahmood; Asim Daud; Adila Batool; Zia-ul-Haq (Asia-Pacific Journal of Atmospheric Sciences, 2014)

New acylated oligosaccharides from Pistacia integerrima - Zia Ullah; Rashad Mehmood; Muhammad Imran; Abdul Malik; Rehana A. Afzal (Natural Product Research, 2013)

Molecular classification of Pakistani collared dove through DNA barcoding - Ali Raza Awan; Emma Umar; Muhammad Zia ul Haq; Sehrish Firyal (Molecular Biology Reports, 2013)

Maize seedling phosphorus nutrition: Allocation of remobilized seed phosphorus reserves and external phosphorus uptake to seedling roots and shoots during early growth stages - Muhammad Nadeem; Alain Mollier; Christian Morel; Muhammad Shahid; Muhammad Aslam; Muhammad Zia-ur-Rehman; Muhammad Ashfaq Wahid; Sylvain Pellerin (Plant and Soil, 2013)

Application of the CSM-CERES-Rice model for evaluation of plant density and irrigation management of transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Hakoomat Ali; Abid Hussain; Axel Garcia y Garcia; Muhammad Azam Khan; Muhammad Zia-Ul-Haq; Mirza Hasanuzzaman; Gerrit Hoogenboom (Irrigation Science, 2013)

Effects of Vitamins, Probiotics, and Protein Level on Semen Traits and Some Seminal Plasma Macro- and Microminerals of Male Broiler Breeders After Zinc-Induced Molting - Rifat Ullah Khan; Zia-ur-Rahman; Ijaz Javed; Faqir Muhammad (Biological Trace Element Research, 2012)

Measurement of radionuclides and absorbed dose rates in soil samples of Peshawar, Pakistan, using gamma ray spectrometry - Hasan M. Khan; Muhammad Ismail; Muhammad Abid Zia; Khalid Khan (Isotopes in Environmental and Health Studies, 2012)

Application of the CSM-CERES-Rice model for evaluation of plant density and nitrogen management of fine transplanted rice for an irrigated semiarid environment - Shakeel Ahmad; Ashfaq Ahmad; Cecilia Manuela Tojo Soler; Hakoomat Ali; Muhammad Zia-Ul-Haq; Jakarat Anothai; Abid Hussain; Gerrit Hoogenboom; Mirza Hasanuzzaman (Precision Agriculture, 2012)

Effect of Zinc and Iron Fortification of the Feed on Liver and Thyroid Function in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; M. Riaz; Muhammad Arshad; Abdul Basit; Tariq Ismail (Biological Trace Element Research, 2011)

Effect of Mineral Fortification on Plasma Biochemical Profile in Rats - Saeed Akhtar; Faqir M. Anjum; Zia Ur Rehman; Munammad Tauseef Sultan; Muhammad Riaz; Anwaar Ahmed (Biological Trace Element Research, 2011)

Liquid chromatographic analysis of halofantrine from dosage form and its metal interaction studies - Najma Sultana; Muhammad Saeed Arayne; Muhammad Nawaz; Zia Ur Rehman (Medicinal Chemistry Research, 2011)

Comparison of SDSM and LARS-WG for simulation and downscaling of extreme precipitation events in a watershed - Muhammad Zia Hashmi; Asaad Y. Shamseldin; Bruce W. Melville (Stochastic Environmental Research and Risk Assessment, 2011)

Expression of rol genes in transgenic soybean (Glycine max L.) leads to changes in plant phenotype, leaf morphology, and flowering time - Muhammad Zia; Bushra Mirza; Salman Akbar Malik; Muhammad Fayyaz Chaudhary (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Plasma homocysteine and DNA damage profiles in normal and obese subjects in the Pakistani population - Shazia A. Bukhari; Muhammad I. Rajoka; Saeed A. Nagra; Zia Ur Rehman (Molecular Biology Reports, 2010)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)

A convenient synthesis of p -substituted 1-arylsulfonyl-pyrrolidin-2-ones - Muhammad Zareef; Rashid Iqbal; Khalid M. Khan; Javid H. Zaidi; Zia-Ullah; Muhammad Arfan (Natural Product Research, 2009)

Facile, economical and direct synthesis of 9-anilinoacridines - Khalid M. Khan; Nosheen A. Rao; Zia-Ullah; Muhammad Ali; Shahnaz Perveen; Muhammad Iqbal Choudhary; Atta-Ur-Rahman; Wolfgang Voelter (Natural Product Research, 2009)

Successful computer guided planned synthesis of (4R)-thiazolidine carboxylic acid and its 2-substituted analogues as urease inhibitors - Khalid Mohammed Khan; Zia Ullah; Muhammad Arif Lodhi; Muhammad Ali; Muhammad Iqbal Choudhary; Atta ur Rahman; Zaheer ul Haq (Molecular Diversity, 2006)